Battery formation protocol

By using ultra-concentrated sodium salt ionic liquid electrolyte and high current density polarization cycle, high conductivity and thin SEI are formed on the hard carbon anode, solving the problems of unevenness and long time in the traditional battery formation protocol, achieving efficient battery formation and excellent battery performance.

CN119790502APending Publication Date: 2025-04-08DEAKIN UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380063250.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The solid electrolyte interface (SEI) formed by existing sodium ion batteries on the hard carbon anode is uneven and thick, resulting in a degradation of battery performance, and the traditional battery formation protocol is long and inefficient.

Method used

An ionic liquid electrolyte with super-concentrated sodium salt is used and SEI is formed on the hard carbon anode through polarization cycles with high constant current density, ensuring that the SEI is thin and conductivity is high.

Benefits of technology

The formation of high-quality SEI in a short time is achieved, the cycle stability and battery performance of sodium ion batteries are improved, and the battery formation time and cost are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119790502A_ABST
    Figure CN119790502A_ABST
Patent Text Reader

Abstract

The formation protocol is 20 or more times faster than a conventional formation protocol, may result in an improved stable high ionic conductivity, low impedance solid electrolyte interface (SEI), less electrolyte consumption and less irreversible capacity loss compared to the conventional formation protocol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to rapid battery formation methods or protocols, particularly sodium ion batteries involving hard carbon anodes. Background Art

[0002] Batteries with high energy density and long life are desirable, especially if they can be manufactured at low cost. Rechargeable sodium-ion batteries are typically assembled in a discharged or "new" or "virgin" state, meaning that the battery is in a pre-cycled state. In the battery manufacturing process, new batteries must be "formed" as the next step. Battery forming is the process of subjecting new batteries (usually 2 / 3 polarization cycles) to an initial set of charge / discharge (polarization cycles) operations at the factory. During the charging process, the positive active material (e.g., sodium oxide) produces transferable sodium transport ions, which diffuse to the negative active material (e.g., carbon, graphite), where they are reduced and "absorbed" into the negative electrode material, which was free of sodium ions (virgin) before charging. During discharge, the reverse reaction occurs, and the stored chemical energy is converted into electrical energy to be used to power the connected load. The charging step and the subsequent discharge step are called a "polarization cycle." During the first polarization cycle, an electrochemical electrolyte interface forms at the electrodes and is formed primarily on the negative electrode in the form of a solid electrolyte interface (SEI), which is a passivation layer formed on the anode surface in all sodium-ion batteries using liquid electrolytes. SEI formation depends strongly on the battery chemistry and electrolyte composition, as it is formed from the decomposition / reduction products of the electrolyte components, which consume a portion of the electrolyte during the first few cycles. Useful formation protocols form a high-quality and robust SEI, which is very important for battery performance, resulting in improved cycling stability, higher capacity, and / or higher coulombic efficiency, all of which are evidence of reduced anode and electrolyte degradation. An ideal SEI provides fast transport for transport ions across the interface while being a good electronic insulator, thereby protecting the electrolyte from further degradation, which would otherwise quickly lead to battery capacity loss. The SEI should be stable under both cycling and aging conditions. SEI formation leads to irreversible consumption of transport ions in the electrolyte during cycling, resulting in a decrease in achievable capacity and an increase in resistance, leading to increased impedance within the cell. Conventionally, the best SEI layer is selectively permeable to the transport ions used and is desired to be as thin as possible, typically only a few nanometers thick, because a thin SEI reduces the resistance to ion transport, thereby supporting optimal battery performance. However, an SEI that is too thin cannot adequately protect the electrolyte from anode reduction. A good SEI is uniformly distributed on the anode surface, completely preventing contact between the anode and the electrolyte, and should also be mechanically strong / tough while being chemically inert to avoid undesirable side reactions.

[0003] Hard carbon (HC) is an anode alternative to graphite that is more suitable for sodium batteries, but is known to have a more complex sodium ion absorption mechanism and SEI formation process. This is due to the reactivity of HC, which results in a thick and non-uniform SEI due to its higher surface area and porosity. A thicker SEI will hinder the diffusion of transport ions, thereby reducing battery performance, while an inhomogeneous SEI supports local side reactions, thereby reducing performance over time. Most HC / SEI studies involve conventional film-forming electrolyte additives, such as hexafluorophosphate or TFSI salts, various carbonates, fluorinated carbonates, or other solvents. The degradation products of these additives always form part of the HC SEI when formed. However, state-of-the-art ester solvent-based sodium ion battery electrolytes (such as propylene carbonate (PC) and ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and diethyl carbonate (DEC)) result in an outermost SEI layer rich in organic matter, making the SEI generally unstable with large charge transfer resistance and high energy barriers for sodium ion transport. Some research groups incorporated ionic liquid / carbonate electrolytes into NIBs and attributed the improvement of the SEI layer to the ionic liquid electrolyte.

[0004] The battery formation / conditioning protocol used in commercial battery manufacturing, which depends on battery chemistry, is usually up to a week to form the necessary strong and uniform interface. Typically, several slow constant current charge-discharge cycles are performed at low currents, with different rest periods at high temperatures. Conventional slow formation is considered to produce the most uniform and stable SEI layer. Typically, very small current densities (e.g., 1 / 10C or 1 / 20C of equivalent low current density) are used for a long time to maximize the insertion of transport metals, and thereby charge the charge capacity into the negative electrode during the formation charge to ensure the formation of a uniform and stable SEI layer. Therefore, the formation time is very slow (e.g., 2 / 3 cycles of 20 to 40 hours per polarization cycle means that it takes 40 to 120 hours to form alone, without rest, etc.). Therefore, the battery production efficiency of conventional protocols is low and the capital cost is high. Current densities exceeding 1 / 1C rates are considered to damage the electrodes due to premature aging, and are therefore considered to be harmful to battery performance and have therefore been avoided during commercial formation. Furthermore, rapid formation may create the risk of dendrites during cycling (via plating), which would damage the cell and degrade performance under normal operation.

[0005] New formation protocols that balance electrochemical performance, manufacturing cost, and time efficiency are needed, especially in the case of batteries involving HC anodes. Sodium-ion batteries (NIBs) are viewed as next-generation lithium-ion battery (LIB) alternatives. The same slow and expensive conventional lithium-ion battery formation protocols are also applicable to NIBs. However, the SEI formed for NIBs is not as stable as its lithium-ion battery counterpart. + and Li +Significant differences between + Increased size, and differences in reactivity make uniform and stable SEI formation for NIBs more difficult. Finally, NIB SEI components exhibit increased solubility, which is a problem for SEI stability. Therefore, knowledge on SEI formation in Li-ion batteries cannot be directly applied to the formation of NIBs, whereas SEI formation in Na batteries has been studied empirically. Overall, the ideal compositional features of the SEI on HC of NIBs are poorly understood.

[0006] Rakov et al. (Chem. Mater. 2022, 34; “Rakov 2022”) reported a lithium deposition / stripping study in a highly viscous ultraconcentrated electrolyte (100 IL) involving high current densities (≥10.0 mA cm -2 Up to 1.0 mAh cm -2 A single lithium metal anode pretreatment step of 200 Å to 100 Å depth of charge (DOC) was found to be beneficial for the SEI composition compared with low-concentration lithium salt-containing IL electrolytes because the SEI composition is Li x (Anion) y (x>y) dominates. However, when a lower viscosity superconcentrated electrolyte (80IL20DME) containing 20 wt% ether cosolvent is used, a more modest pretreatment step current density (6.0 mA cm -2 / 1.0mAcm -2 ) leads to better optimized lithium deposition morphology and even at 15.0 mA cm -2 / 1.0mAh cm -2 Optimal cycling performance is also achieved at extreme currents of 200 Å. Since the optimized current density for viscous electrolytes is different from that for more fluid electrolytes, Rakov 2022 suggests that separate, tailored pretreatment protocols should be adopted depending on the electrolyte composition, but does not indicate how such a protocol should be derived. It is worth noting, however, that the focus of Rakov 2022 is limited to SEI formation at lithium metal anodes in symmetric cells after a single pretreatment step, and does not address the formation of SEI in HC anodes in NIBs. As explained, due to the unpredictable nature of SEI formation on HC in NIBs, Rakov 2022 does not teach anything valuable about SEI formation in NIB systems using hard carbon anodes.

[0007] Rakov 2020 (Nature Materials, 19, 2020, 1096-1101) applied different negative electrode polarizations at 50 °C as pretreatments before long-term electrochemical cycling in sodium symmetric batteries based on C3mpyrFSI IL, which contained 50 mol% NaFSI salt. -2Five short cycles were performed at three different current densities, with a depth of charge of 0.1 mAh cm per step. -2 After preconditioning, each test cell was subjected to -2 The cycle was further repeated for 20 cycles at a current density of 5.0 mA cm -2 The cycle was repeated for 10 cycles. -2 The cell pre-treated under 0.1 mA cm resulted in the largest initial polarization potential and the shortest deposition time, and for the subsequent -2 and 1.0mAcm -2 The cycle under 0.1 mA cm shows the smallest overpotential among the three batteries. -2 and 1.0 mA cm -2 Cells preconditioned at lower currents either failed due to short circuits or exhibited unstable voltage profiles. No information on HC anode SEI formation in NIBs. As explained, the Rakov 2020 teaching involving Na metal symmetric cells does not provide information on HC SEI formation in Na-HC systems in NIB cells due to the unpredictability of SEI formation on HC in NIBs.

[0008] Recently, Kishore et al. (Chem. Commun., 2020, 56, 12925-12928) acknowledged that the formation and conditioning processes of lithium-ion batteries are among the least understood, and even less is known about NIBs. Kishore then reported a formation protocol that reduces the formation time and maximizes the cycle life in NIBs containing a Na layered oxide cathode and a HC anode. The formation involves a series of low currents (0.12 mA cm) within various target voltage windows. -2 , 10mA g cat -1 ) cycles, applied to five charge-discharge cycles performed over different voltage windows. Protocols F4 and F5 involved narrow voltage subsets of the standard voltage window and were performed in voltage windows 1.0-1.8 and 1.8-2.6 V and recorded the shortest formation times of 6 hours and 17 hours, respectively. However, F4 and F5 cells showed the worst cell performance in terms of capacity retention after 150 cycles (51.1% and 54.3%, respectively). The best result was obtained with F2 formed at low current and voltage between 3.6-3.8 V, which had a capacity decay of 9.2% and resulted in a formation time of 42 hours. Kishore demonstrated the unpredictability of SEI formation on HC anodes in NIBs and the complexity involved in many experimental formation protocols, which may not be suitable for commercial / industrial applications.

[0009] As mentioned above, the propensity for SEI formation in Li-ion batteries and in Na / Na symmetric cells cannot be directly transferred to NIBs for various reasons as mentioned above. Conventional thinking involving multiple slow steps at low current densities is usually adopted to ensure proper formation of an optimal SEI on the HC anode of a NIB cell. Summary of the invention

[0010] In a first aspect, the present invention provides an electrochemical cell comprising:

[0011] - an ionic liquid electrolyte containing a super-concentrated sodium salt, comprising at least one ionic liquid and at least one sodium salt,

[0012] wherein the concentration of the sodium salt in the super-concentrated sodium salt ionic liquid electrolyte is 75% or more of its saturation limit in the ionic liquid electrolyte;

[0013] a counter electrode or positive electrode comprising an electrochemically oxidizable material which releases sodium ions from the material into the electrolyte of the superconcentrated sodium salt in the cell during the sodiation step or charging step, and

[0014] a hard carbon working electrode or negative electrode which absorbs sodium ions received from the superconcentrated electrolyte at the hard carbon negative electrode as reduced sodium stored in the hard carbon during a sodiation step or a charging step, wherein

[0015] (a) The hard carbon negative electrode includes a formed solid electrolyte interface (SEI) which is:

[0016] - Essentially free of low-order / short-range sulfur (S8 2- To S 2- ) substances, for example, as determined by XPS testing and etching studies;

[0017] and optionally

[0018] - substantially free of nitrogen atoms, as determined, for example, by XPS testing and etching studies;

[0019] and / or

[0020] (b) After the first formation cycle, the solid electrolyte interface (SEI) / hard carbon electrode has a bond with SEI (R int )-related interfacial resistance, as determined by electrochemical impedance spectroscopy.

[0021] In a second aspect, the present invention provides a use of a super concentrated ionic liquid electrolyte in a battery, wherein the sodium salt concentration in the super concentrated ionic liquid electrolyte is 75% or more of its saturation limit, and the battery comprises a hard carbon working electrode or a negative electrode to form a SEI on the hard carbon electrode, wherein:

[0022] (a) The hard carbon anode includes a formed solid electrolyte interface (SEI), which is:

[0023] - Essentially free of low-order / short-range sulfur (S8 2- To S 2- ) substances, for example, as determined by XPS testing and etching studies;

[0024] and optionally

[0025] - substantially free of nitrogen atoms, as determined, for example, by XPS testing and etching studies;

[0026] and / or

[0027] (b) After the first formation cycle, the solid electrolyte interface (SEI) / hard carbon electrode has a 200 ohm or less bond with the SEI (R int )-related interfacial resistance, as determined by electrochemical impedance spectroscopy.

[0028] In a third aspect, the present invention provides a method for forming a battery, comprising the steps of:

[0029] -Provide an original battery based on sodium metal ion electrochemistry, the new battery comprising:

[0030] a counter electrode or positive electrode comprising an electrochemically oxidizable material which releases sodium ions from the material into a superconcentrated electrolyte in the cell during a sodiation step or a charging step,

[0031] - a hard carbon working electrode or negative electrode, which absorbs sodium ions received at the hard carbon negative electrode from the superconcentrated electrolyte during the sodiation step or charging step as reduced sodium stored in the hard carbon, and,

[0032] - an ionic liquid electrolyte containing a super-concentrated sodium salt, comprising at least one ionic liquid and at least one sodium salt,

[0033] wherein the sodium ion concentration in the superconcentrated ionic liquid electrolyte is 75% or more of its saturation limit in the electrolyte;

[0034] - generating a formed target cell by polarizing the pristine cell for up to 5 formation cycles at a high constant current density of 1 / 2C to 5C, preferably 2C, within the full voltage window of the cell, to produce a formed SEI by reducing the electrolyte on the hard carbon electrode,

[0035] in,

[0036] (a) The hard carbon anode includes a formed solid electrolyte interface (SEI), which is:

[0037] - Essentially free of low-order / short-range sulfur (S8 2- To S 2- ) substances, for example, as determined by XPS testing and etching studies;

[0038] and optionally

[0039] - substantially free of nitrogen atoms, as determined, for example, by XPS testing and etching studies;

[0040] and / or

[0041] (b) After the first formation cycle, the solid electrolyte interface (SEI) / hard carbon electrode has a 200 ohm or less bond with the SEI (R int )-related interfacial resistance, as determined by electrochemical impedance spectroscopy.

[0042] The inventors found that high current density drives SEI formation, and the SEI produced on hard carbon (HC) is surprisingly highly conductive and can promote Na + Ions diffuse across electrode / electrode boundaries. In some embodiments, an improved SEI and associated improved battery performance is demonstrated by stable and high performance cycling using a C rate of 1 / 2C or slower (e.g., 1 / 5C), with the battery exhibiting a coulombic efficiency greater than 99.0%, preferably 99.2% or greater, preferably 99.3% or greater, preferably 99.4% or greater, preferably 99.5% or greater, preferably 99.6% or greater, preferably 99.7% or greater, preferably 99.8% or greater, preferably 99.9% or greater when cycling at the nominal rate (after formation is complete). For example, in some embodiments, most preferably after 50, 100, 200 or 300 cycles or more, the battery cycled at a nominal 1 / 10C battery rate (after formation) exhibits a CE of 99.5% or greater, preferably 99.6% or greater, more preferably 99.7% or greater, and most preferably 99.8% or greater. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Embodiments of the present invention will now be described by way of example only with reference to the accompanying drawings, in which:

[0044] Figure 1 shows the voltage-time diagrams of the first five cycles of all cells at the same time scale (a) and different time scales (b); constant current charge-discharge curves of the Na / HC cell at different C rates (1 / 10C, ​​1C and 2C) at the first (c) and fifth cycles (d); amplified constant current charge / discharge curves of the three differently formed cells at the sixth cycle (e); the first and fifth constant current charge and discharge of the Na / HC half-cell at a current density of 0.1C (1C = 300mAh / g) (f); CV curves of the Na / HC half-cell at the first and fifth cycles at a scan rate of 0.1mV / s (g);

[0045] Figure 2 shows the dQ / dV of Na / HC batteries at different C rates in the 1st cycle (d)–(f) and the 5th cycle (g)–(i) versus the V curves of Na / HC batteries at different C rates, 2C batteries in the 2nd–4th cycles (h)–(k); 1C batteries in the 2nd–4th cycles (k)–(m); 1 / 10C batteries in the 2nd to 4th cycles (n)–(p);

[0046] Figure 3 shows the cycling stability of Na / HC half-cells with different formation protocols. Long-term discharge capacity cycling of three cells at 1 / 2C (a) and 1 / 5C (g); Long-term charge capacity cycling of three cells at 1 / 2C (b) and 1 / 5C current density (d); Coulombic efficiency of Na / HC cells cycled at 1 / 2C (b) and 1 / 5C current density (h); Insets in (a, b, g, h) are selected cycles of cycling and CE. Cumulative irreversible capacity of three formation cells at the beginning of 10 cycles (e); Long-term cycling of 2C formation cell at 1 / 2C current density (f); Constant current charge / discharge curves of 2C formation cell at the 50th and 300th cycles (i); Cycling stability of Na / HC cells at different formation rates (2C, 3C and 10C, 1C=300mA), and 1 / 2C for long-term cycling; Inset is the enlarged area of ​​the 20th-40th cycle stability of 2C and 3C cells (j);

[0047] Figure 4 Three-electrode EIS measurements of HC anodes with different formation processes (2C, 1C, and 1 / 10C) in Na / HC batteries for 5 cycles (ac) are shown; EIS resistance fitting results of three batteries after the 1st, 2nd, and 5th formation cycles (d–f);

[0048] Figure 5 shows the XPS spectra of the HC anode after the first five formation cycles detected at three different C rates: C 1s (a), N 1s (b), and S2p (c). The inset in (c) is a magnified region of the 1 / 10C formation cell between 156–164 eV, where small sulfur species are present; C1s spectra of the original sample, 1 / 10C sample, 1C sample, and 2C sample (d); O1s spectra of the original sample, 1 / 10C sample, 1C sample, and 2C sample (e); C1s spectra of the three formation protocols after different etching times of 0 min, 2 min, 10 min, and 40 min (f)-(h); Figure 6 shows the XPS etching depth distribution of the 2C formation cell after 5 formation cycles (a), the 1C formation cell after 5 formation cycles (b), the 1 / 10C formation cell after 5 formation cycles (c), and the original cell (d); Schematic diagram of SEI formation on hard carbon anodes with different formation units (e); N1s etching depth of 1 / 10C cell hard carbon (f), with a magnified region between 400–404 eV (g);

[0049] Figure 7 The charge-discharge curves of the sixth formation cycle of the test cell formed at 1 / 10C are shown, and the target cells formed at 1C and 2C are shown in FIG. Figure 7 (a) In. Figure 7 (b) shows the extended area of ​​the curve in (a);

[0050] Figure 8 The irreversible capacity and cycle number of the formed 1 / 10C test cell and the formed 1C cell (a) and 2C target cell (b) are shown; the rate capability test of the formed 2C and 1 / 10C cells at different current densities of 1 / 10, 1 / 5, 1 / 2, 1, 2, 4C (1C = 300mAh / g) (c), and the magnified rate capability of the formed 2C and 1 / 10C cells at 1 / 10, 1 / 5 and 1 / 2C. The mass loading of HC is 0.8mg / cm 2 (d);

[0051] Fig. 9 A graph showing the cumulative irreversible capacity during different cycles is shown;

[0052] Fig.10 The fitted data and raw EIS data of different formed cells at different cycles are shown: 2C cell at 1st, 2nd and 5th cycle (ac); 1C cell at 1st, 2nd and 5th cycle (df); 1 / 10C cell at 1st, 2nd and 5th cycle (gi);

[0053] Fig.11 The results of cycling the electrode 5 times under different C-rate formation protocols are shown. 23Na(a) and 19 F (b) MAS NMR spectra (electrode in charged state), HC immersed in electrolyte, and also in pure ionic liquid. DETAILED DESCRIPTION

[0054] Detailed description of the invention

[0055] The present invention relates to an electrochemical cell comprising:

[0056] - an ionic liquid electrolyte containing a super-concentrated sodium salt, comprising at least one ionic liquid and at least one sodium salt,

[0057] wherein the sodium ion concentration in the superconcentrated ionic liquid electrolyte is 75% or more of its saturation limit in the electrolyte;

[0058] a counter electrode or positive electrode comprising an electrochemically oxidizable material which releases sodium ions from the material into a superconcentrated electrolyte in the cell during a sodiation step or a charging step, and

[0059] - a hard carbon working electrode or negative electrode, which absorbs sodium ions received from the superconcentrated electrolyte at the hard carbon negative electrode during the sodiation step or charging step as metallic sodium stored in the hard carbon, and,

[0060] The hard carbon negative electrode includes a formed solid electrolyte interface (SEI), and the solid electrolyte interface is one or more of the following:

[0061] - In XPS testing and etching studies, the peak with a binding energy of approximately 396 eV confirmed the complete absence of nitrogen atoms, and

[0062] - In XPS testing and etching studies, the peaks at binding energies of about 164 eV to 160 eV confirmed the complete absence of low-order / short-range sulfur (S8 2- To S 2- )substance.

[0063] The inventors have discovered that the improved SEI is a thinner and / or more ionically conductive SEI, and / or one in which the formed SEI is associated with a favorable (surprisingly low / reduced) interfacial resistance, manifested as low impedance, compared to cells formed at conventional formation rates / current densities. The inventors believe that the absence of low-order / short-range sulfur (S8 2- To S 2-) species, resulting in a thinner SEI layer, which supports faster Na+ diffusion through the SEI layer. It is also believed that the absence of one or more nitrogen atomic species in the SEI composition may also be beneficial, as the XPS studies described herein show many compositional differences between the SEI on hard carbon formed at low current density (1 / 10C) and high current density (1C and 2C).

[0064] In general, why are the inorganic substances described in this article considered to be + Having a lower diffusion barrier and expected to improve Na+ migration kinetics, the inventors found that the presence of more reduced sulfur species in the SEI makes the SEI layer thicker and actually increases the Na + diffusion pathway and reduces the reaction kinetics. Other species in the SEI also increase the thickness and size of the Na+ diffusion path, such as nitrogen atoms as determined by XPS analysis. The inventors have now discovered that the SEI without these species actually has a thinner, more porous or lower density SEI or at least one SEI layer with stronger ion conductivity formed on the hard carbon. The result is that the sodium ion diffusion path is shorter and / or has more ion conductivity characteristics. The prior art also does not teach that one or more of the constituent SEI characteristics described herein are important for improving SEI formation and excellent battery performance in sodium hard carbon batteries.

[0065] In some embodiments, the thickness of the SEI can be determined or at least approximated by etching studies, such as etching to observe the time of the XPS signal that matches the surface of the original electrode. Other methods can be used to measure the SEI thickness, including electrochemical or electron microscopy methods that can be used. Typically, the thickness of the conventionally formed SEI is hundreds of nanometers. The inventors have published an etching study report on these compositions (e.g., ACS Appl. Mater. Interfaces 2021, 13, 4, 5706-5720), which describes the use of electrochemical methods to estimate the SEI thickness on page 5710. The relevant parts thereof are incorporated herein by reference.

[0066] In some embodiments, the ionic conductivity of the SEI and / or the interfacial resistance of the SEI can be determined or inferred by the well-known electrochemical impedance spectroscopy (EIS) method. After the first formation cycle, the preferred solid electrolyte interface (SEI) / hard carbon electrode has a resistance to the SEI (R) of less than 300 ohms, more preferably less than 200 ohms. int ) associated with the SEI, as determined by electrochemical impedance spectroscopy. At the end of the formation cycle, the preferred solid electrolyte interface (SEI) / hard carbon electrode has an interfacial resistance with the SEI (R) of less than 75 ohms and in some cases less than 50 ohms. int ) related interfacial resistance, which indicates that Na +Easily transported through the SEI of the present invention.

[0067] Compared with the conventionally formed SEI, the above-mentioned battery performance characteristics in the methods of the first and second aspects show that the formation of the SEI has been substantially complete and stably improved. In addition, or separately, the substantially complete and stable improved SEI is an SEI that forms a thinner or more ionically conductive SEI layer on the surface of the active material. The substantially complete and stable improved SEI is an SEI with a shorter metal ion diffusion path and / or an SEI with more ion conductivity characteristics. It is believed that the shorter metal ion diffusion path is due to a thinner, or porous or less dense SEI, or a combination of one or more of these factors, which generally lead to a shorter ion diffusion path compared to the SEI formed in other equivalent batteries applying the above-mentioned conventional formation conditions. The generation of this improved SEI is a surprising discovery, because the conventional thinking of SEI formation shows that it is necessary to form a thick and comprehensive SEI layer and / or a layer involving film-forming additive components added to the electrolyte very slowly to ensure optimal battery performance. The current results are completely opposite, using ultra-concentrated ionic liquid electrolytes at high current rates and fast formation times to form better SEIs with improved ionic conductivity / shorter ion diffusion paths (thinner, or less dense, or more porous, or all of these characteristics, etc.), which helps improve battery performance while consuming less electrolyte in SEI formation. In addition, since the irreversible capacity loss of the battery is less when the improved SEI is formed, the battery of the present invention has more starting electrolyte than conventional batteries, and therefore will experience slower capacity decay due to aging, and is therefore expected to have a longer life.

[0068] Suitably, the SEI is formed according to the optimized battery formation conditions described herein.Also described herein are target batteries formed obtainable or obtainable by the methods of the present invention.

[0069] Ideally, the improved SEI in the formed target cell has a composition having an outer layer that includes more CN species than the SEI of the formed test cell, as indicated by XPS testing and / or etching studies.

[0070] XPS and etching studies show that the SEI composition of the test cells formed at 1 / 10C current density has features attributed to nitrogen atoms (with a binding energy of about 396 eV in the tests described herein). Ideally, XPS analysis of the SEI composition of cells formed at 1C and 2C by the method of the present invention does not have features attributed to nitrogen atoms at about 396 eV.

[0071] As indicated by XPS testing and etching studies, preferably, the improved SEI in the target cell is formed without the presence of small sulfur-containing species (low-order / short-range sulfur (S8 2- To S 2- )) or contain fewer small sulfur-containing species than found in the SEI of the formed test cells. These species are associated with the thicker SEI in the cells formed at 1 / 10C, ​​which has increased Na + diffusion pathways and reduce reaction kinetics.

[0072] Preferably, the improved SEI in the resulting target cell comprises a C to O ratio of 1 or greater after 40 minutes of etching.

[0073] The above differences in composition of the SEI formed at 1 / 10C rate and the SEI formed at 1C and 2C rates confirm that the SEI is different in composition. These differences are related to the performance improvements observed in cells formed at higher current densities.

[0074] Ideally, the improved SEI in the formed target cell is a thinner layer than the SEI of the formed test cell, as indicated by XPS testing and etching studies and / or EIS measurements.

[0075] Also described herein is a method for determining optimized cell formation conditions for forming a cell formation method for forming an improved SEI on a hard carbon anode in a sodium ion electrochemical cell, preferably for a total time of 20 hours or less, preferably 10 hours or less, preferably 5 hours or less, more preferably 2.5 hours or less, the method comprising the steps of:

[0076] - providing two or more new (original) batteries based on sodium ion electrochemistry, wherein each new battery comprises:

[0077] o a counter electrode comprising an electrochemically oxidizable material capable of releasing sodium ions into a super-concentrated sodium salt / ionic liquid electrolyte in the cell during cell polarization, and

[0078] o a hard carbon working electrode for absorbing sodium metal ions received at the hard carbon working electrode from the super-concentrated electrolyte as reduced sodium stored in the hard carbon working electrode,

[0079] wherein the superconcentrated sodium salt / ionic liquid electrolyte comprises an ionic liquid and at least one sodium salt, wherein the concentration of the sodium salt is 75% or more of its saturation limit in the electrolyte;

[0080] - generating a formed test cell by applying a cell formation method to a first new test cell to generate an SEI on a hard carbon working electrode of the new test cell, thereby generating a formed test cell comprising:

[0081] o polarizing the first new test cell at a predetermined first current density within the full voltage window of the new test cell to achieve the full discharge capacity of the new test cell (e.g., a current density equal to 1 / 10C or less, or 1 / 20C or less) within a single discharge period of at least 10 hours, more preferably at least 20 hours, and optionally

[0082] o determining the presence and / or absence of one or more markers associated with the formation of a substantially intact and substantially stable SEI on the hard carbon electrode of the formed test cell during the recorded corresponding charge and discharge cycles or related analysis; and if necessary,

[0083] o repeating the polarization cycling step one or more times for the formed test cell at the same first current density or at a different higher or lower predetermined formation current density until the presence and / or absence of one or more markers are observed in the recorded corresponding charge and discharge cycles or related analyses and such markers are associated with the formation of a substantially complete and stable SEI on the hard carbon electrode of the formed test cell;

[0084] - producing a target cell with improved formation of a SEI on a working electrode of the formed target cell by applying an improved cell formation method to a new first target cell, comprising:

[0085] o polarizing the new first target battery at a second current density within the full voltage window of the new first target battery, the second current density being higher than the current density for the new test battery and predetermined to achieve the cut-off discharge potential limit of the battery and the final discharge capacity of the new first target battery in a single discharge of less than 5 hours, a single discharge of less than 2 hours, preferably a single discharge of 1 hour or less, and more preferably a single discharge of 30 minutes or less, and

[0086] o determining the presence and / or absence of one or more markers associated with substantially complete and substantially stable improved SEI formation on the hard carbon electrode of the formed first target cell during the recorded corresponding charge and discharge cycles or related analysis; and if necessary,

[0087] o repeating the polarizing step one or more times at the same predetermined second current density or a different higher or lower predetermined formation current density on the resulting formed first target battery until the presence and / or absence of the one or more markers indicates that substantially complete and substantially stable improved SEI formation has occurred on the hard carbon electrode of the formed first target battery,

[0088] Among them, the improvement of the SEI formed on the hard carbon of the formed first target battery is manifested as the formed first target battery exhibiting a higher specific capacity and / or Coulombic efficiency during cycling at a nominal C rate compared to the specific capacity and / or Coulombic efficiency exhibited by the formed first test battery at the same nominal C rate.

[0089] In addition to one or more of the above SEI composition features, preferably, the improved SEI on the hard carbon in the target battery is formed to have an SEI composition further defined by:

[0090] - having an outer layer comprising more CN material than the SEI of the formed test cell as indicated by XPS testing and / or etching studies at the same etching time;

[0091] - having a composition including a ratio of C to O of 1 or more after etching for 40 minutes.

[0092] The comparison at the nominal C-rate occurs in formed cells where all other conditions are the same, e.g. the same number of polarization steps are applied to both. The cut-off discharge potential limit of a cell is the specified voltage limit at which the discharge of the cell is considered complete and is usually the voltage limit that allows the maximum useful capacity of the cell to be achieved under typical operating conditions, which will result in the best performance of the cell in question and depends on the cell chemistry. There is a corresponding cut-off charge potential limit for the cell at which the cell is considered to be fully charged. Determining the appropriate cut-off potential limit for any cell is within the normal remit of a skilled electrochemist. The C-rate is a measure of the rate at which a cell is charged or discharged relative to its maximum capacity. For example, 1C means the current required to be applied or drained to the cell in 1 hour to fully charge or discharge it, for 1 / 10C the current is applied / drained in 10 hours and at 2C the current is applied / drained in 30 minutes to fully charge or discharge the cell to the selected voltage cut-off point. The C-rate is used here because the amount of active material used in the electrode is small. However, for electrodes using large amounts of active material, the current density required to result in a complete charge / discharge can be easily determined electrochemically.

[0093] In some embodiments, batteries according to the present invention are capable of operating at temperatures between -20°C and 150°C, for example, between -10°C and 150°C, between 0°C and 150°C, between 0°C and 125°C, between 0°C and 100°C, between 0°C and 75°C, between 0°C and 50°C, or between 0°C and 25°C.

[0094] Preferably, the optimization method of the present invention may further include the following additional steps:

[0095] - producing a further formed second target cell with an improved SEI on a working electrode of the formed second target cell by applying a cell formation method to one or more new target cells, comprising:

[0096] o polarizing the new second target battery within the full voltage window of the new second target battery at a third current density, the third current density being higher than the second current density and predetermined to achieve the cut-off discharge potential limit of the battery and the final discharge capacity of the new second target battery in a period less than that selected by the method of the first aspect, and

[0097] o determining the presence and / or absence of one or more markers associated with substantially complete and substantially stable further improved SEI formation on the hard carbon electrode of the formed second target cell during the recorded corresponding charge and discharge cycles or related analysis; and if necessary,

[0098] o repeating the polarizing step one or more times at the same predetermined third higher current density or at a different higher or lower predetermined formation current density on the resulting formed second target battery until the presence and / or absence of the one or more markers indicates that substantially complete and stable improved SEI formation has occurred on the hard carbon electrode of the formed second target battery,

[0099] The improvement of the SEI formed on the hard carbon of the formed second target battery is manifested as: the second target battery so formed exhibits a higher specific capacity and / or a higher Coulombic efficiency during cycling at the nominal C rate compared to the specific capacity and / or Coulombic efficiency exhibited by the formed test battery and the formed first target battery at the same nominal C rate. It should be understood that the comparison at the nominal C rate occurs in the formed battery with all other conditions being the same, for example, the same number of polarization steps are applied to both.

[0100] Further improvements in the method may be achieved by repeating the steps on yet another new third target cell or one or more subsequent new additional target cells as desired, further improvements in the SEI formed thereby being indicated by observing further improved performance at the nominal C-rate of the cell.

[0101] In some embodiments, up to 5 or 5 formation cycles are required to produce a substantially complete and substantially stable SEI. It should be understood that for each of the 5 polarization cycles, for a single discharge phase, each cycle involves a period of at least 10 hours, which will require a total time of 5×20 hours, i.e., a total formation time of 100 hours. In contrast, for each of the 5 polarization cycles, for a single discharge phase, each cycle involves a period of 5 hours or less, which will require a total time of 5×10 hours, i.e., a total formation time of 50 hours, which is half the total time of the conventional formation protocol. Similarly, in contrast, for a single discharge phase in 5 polarization cycles, each cycle involves a period of at least 30 minutes, which will require a total time of 5x0.5 hours, i.e., a total formation time of 2.5 hours, which is 40 times faster than the nominal C rate cycle formed by the equivalent battery within a total time of 100 hours, while producing better performance.

[0102] Also described herein is a cell formation method for forming an improved SEI on a hard carbon anode in a sodium ion electrochemical cell in a total time of 20 hours or less, preferably 5 hours or less, more preferably 2.5 hours or less, comprising the steps of:

[0103] - Provide a new battery based on sodium ion electrochemistry, the new battery comprising:

[0104] o a counter electrode comprising an electrochemically oxidizable material capable of releasing sodium ions into a superconcentrated electrolyte in the cell during cell polarization, and

[0105] o a hard carbon working electrode for absorbing sodium metal ions received at the hard carbon working electrode from the super-concentrated electrolyte as reduced sodium stored in the hard carbon working electrode,

[0106] wherein the super-concentrated sodium ion ionic liquid electrolyte comprises an ionic liquid and at least one sodium salt, wherein the concentration of the sodium salt is 75% or more of its saturation limit in the electrolyte;

[0107] - producing a formed target battery with an improved SEI by applying a battery formation method on a working electrode of the formed target battery,

[0108] By polarizing the new target battery at a predetermined formation current density, for a single discharge, the battery cut-off discharge potential limit and the final discharge capacity of the new target battery are achieved in less than 5 hours, less than 2 hours, preferably 1 hour or less, more preferably 30 minutes or less.

[0109] determining the presence and / or absence of one or more markers associated with the formation of a substantially complete and stable SEI on the hard carbon electrode during the recorded corresponding charge-discharge cycles or related analysis; and if necessary,

[0110] repeating the polarization step one or more times at the same predetermined formation current density on the resulting formed target battery until the presence and / or absence of one or more markers indicates that substantially complete and stable improved SEI formation has occurred on the hard carbon electrode of the formed target battery,

[0111] The predetermined formation current density and / or number of polarization cycle repetitions required to produce the improved SEI is determined by the method of the first aspect.

[0112] Preferably, in the method of the present invention, cell polarization occurs by galvanostatic charging and discharging of each cell.

[0113] Electrochemical impedance spectroscopy (EIS) can be used to demonstrate the interfacial resistance of hard carbon surfaces at different current densities.

[0114] Also described herein are target batteries formed obtainable and / or obtained by the method of the invention.Preferably, the SEI composition of the battery is defined according to the first aspect above.

[0115] The inventors have developed a new formation protocol for improved SEI formation and improved electrochemical cell performance in sodium-ion based batteries comprising a hard carbon working electrode (or negative electrode in the battery) and a super-concentrated sodium salt / ionic liquid electrolyte. The invention extends to batteries produced by the formation method as described herein, using unconventional high current densities in the formation polarization cycles involving the full voltage window of the battery in question. This concept was demonstrated by half-cell studies of sodiating the hard carbon negative electrode, although the hard carbon is suitable for use in full-cell sodium-ion batteries. Using the method of the invention, sodiation of the original hard carbon is accompanied by essentially complete SEI formation during the first formation cycle, and in some cases, is completely complete within the first few formation cycles, typically after 5 formation cycles. It should be understood that since the electrochemical cell has undergone at least one polarization cycle, and in some embodiments has undergone up to 10 polarization cycles, preferably up to 10, up to 9, up to 8, up to 7, up to 6, up to 5, up to 3 formation cycles, a SEI is formed between the electrode surface and the electrolyte (at the interface) on the hard carbon electrode during the formation process. A method that preferably has fewer polarization cycles to form a substantially complete and substantially stable SEI is preferred because it results in a shorter total formation time.

[0116] The inventors have also developed a method for determining the optimal formation conditions / parameters required for use in the preferred formation methods of the present invention, wherein the desired degree of SEI formation can be achieved within an unconventionally short total formation time period of 20 hours or less, preferably 5 hours or less, more preferably 2.5 hours or less, involving 5 complete formation cycles to ensure completely complete SEI formation. However, in some methods, the formation cycle is even shorter, wherein the SEI is completely formed after only one or two high current density polarization cycles as described herein. The improved method can produce a substantially complete and substantially stable SEI formation by applying about 1 or 2 to 5 formation cycles as described herein, wherein it should be understood that each polarization cycle includes a single discharge of 5 hours or less, preferably a single discharge of 2 hours or less, preferably a single discharge of 1 hour or less, more preferably 30 minutes or less, and in some cases a single discharge step of 15 minutes or less of the discharge phase. It should be understood that the high current density (1 / 2C to 5C) required to support such rapid cycling means that the capacity of the battery at the cut-off potential limit is relatively low compared to the full discharge capacity that can be achieved using conventional polarization / cycling rates (single discharge of at least 10 hours, more preferably single discharge of at least 20 hours). Since conventional formation methods use 2 / 3 of such slow cycles, the total formation time requires about 40 to 120 hours. In contrast, the formation method of the present invention is much shorter, thereby forming a substantially complete and stable SEI in about 5 cycles within a single discharge of, for example, 5 hours or less, preferably 2 hours or less, preferably 1 hour or less, more preferably 30 minutes or less, resulting in a total formation time of only 20 hours or less, preferably 5 hours or less, more preferably 2.5 hours or less, depending on the current density selected for the method.

[0117] Desirably, the method does not include a rest period between consecutive charge and discharge cycles or between consecutive complete cycles of a single charge and discharge cycle. In some preferred embodiments, complete and stable SEI formation occurs in 4 formation cycles or less, preferably 3 formation cycles or less, preferably 2 formation cycles or less, and in some particularly preferred cycles, after 1 formation cycle.

[0118] In some preferred embodiments, the formation protocols described herein can shorten the SEI formation and conditioning time on the hard carbon negative electrode, preferably at least about 10 times, preferably at least about 15 times, and more preferably about 20 times (e.g., about 20 times faster than conventional formation methods), in some cases up to 38 times faster, compared to conventional formation protocols (e.g., involving current densities that give full discharge capacity or current density equivalent at a rate of 1 / 10C or less or 1 / 20C or less). The cost savings and efficiency improvements brought about by the methods of the present invention are obvious.

[0119] Thus, the present invention provides a new, unconventional battery formation method, including the formation of an improved SEI on a hard carbon electrode in a NIB cell, with a total time of 20 hours or less.

[0120] An improved SEI that is substantially complete and substantially stable and formed in a very short time is a high performance / improved SEI that is at least as good as an SEI formed in the same cell (same chemistry, materials, manufacturing, batch, etc.) using a conventional but much slower formation method as described above (e.g., 2 / 3 polarization cycles at 1 / 10C or 1 / 20C rates). By "at least as good" is meant that the SEI will have the same (if not better (higher)) ionic conductivity, and / or the same (if not better (lower)) impedance as an SEI formed using a conventional formation method, the conventional formation method comprising polarization using a single discharge of at least 10 hours, more preferably a single discharge of at least 20 hours (all other conditions being the same). However, the preferred formation method of the present invention produces an improved SEI that is substantially complete and substantially stable for a total time of 20 hours or less, which has been found to result in an SEI having higher ionic conductivity and / or lower impedance than an SEI formed using a conventional formation method as described above. Thus, the improved SEI of the present invention is compositionally different, and / or structurally different, and / or mechanically different, and / or chemically different, such as composition, physical properties such as one or more of thickness, porosity, density, etc., and electrical properties such as impedance and sodium ion conductivity, compared to the SEI of an equivalent cell formed at a much slower rate. It is believed that the SEI of the present invention has one or more of the following characteristics: substantially free of nitrogen atomic species, such as identified by XPS, such as identified by a peak at a binding energy of about 396 eV in XPS testing and etching studies, and low order / short range sulfur (S8 2- To S 2-) material, such as identified by XPS, such as identified by peaks at binding energies of about 164 eV to about 160 eV in XPS testing and etching studies. In addition, the formation methods described herein result in the formed batteries (due to improved SEI formation and reduced electrolyte consumption and less associated irreversible capacity loss during the formation process) exhibiting superior performance compared to conventionally formed batteries at the above-mentioned rates. Advantageously and surprisingly, the observed improved performance improvements are obtained despite the formation time being about 20 times faster than conventional formation protocols (e.g., using formation cycles involving single discharge times of 10 hours or more, and more typically single discharge cycles of 20 hours, with good SEI formation requiring at least 2 or 3 discharge cycles). The results are surprising because the method goes against conventional thinking in the art, which would result in not using very high current densities during formation. There is also no teaching in the prior art that the compositional SEI characteristics described herein are important for improving SEI formation and excellent battery performance in sodium hard carbon batteries.

[0121] Battery formation conditions

[0122] The method involves the steps of producing a formed test cell by applying a cell formation method to a new cell to generate a ("conventional") SEI on the working electrode of a first new cell, whereby the test cell formed is subjected to a set of conventional formation method conditions at a typical slow / low rate, the typical slow / low rate being a conventional rate in which the discharge step of a single polarization cycle takes 10 hours or longer, or even 20 hours or longer. It is used for a single discharge step of a single polarization cycle. Implementing a conventional cell formation step is an optional but useful step because it provides an indication of SEI behavior at low current densities (i.e., slow rates, such as 1 / 10C or 1 / 20C) for typical SEI formation occurring under conventional conditions. This indication is useful for setting the initial improved formation conditions according to the present invention, which are expected to involve shorter discharge cycles possible at higher current densities. This allows the higher current densities used in the formation method of the present invention to be easily determined. For example, an electroanalytical study of the first formation method applied to the first new test cell can also provide information about the nature, stage and integrity / stability of SEI formation at conventional rates, including identification of one or more markers indicating that SEI formation is occurring and / or the extent of SEI formation, such as the degree of integrity and / or stability of the SEI formed, and information about the ionic conductivity and / or impedance of the SEI so formed. These markers can be used to compare the SEI formation in the target battery to which the formation method is applied, and can help identify the formation of a substantially complete and stable SEI formed under the higher rate / current density conditions used in the method of the present invention. They also provide a basis for comparing the properties and / or performance of the improved SEI with the conventionally formed SEI, demonstrating the advantages of the present invention. Therefore, the method of the first aspect may involve establishing a baseline for a "conventionally" formed test cell. Therefore, in this case, the method involves the following steps:

[0123] A first new test cell is polarized within the full voltage window of the new test cell at a predetermined first current density to achieve the full discharge capacity of the cell within a single discharge period of at least 10 hours, more preferably a single discharge period of at least 20 hours (e.g., a current density equal to a 1 / 10C or 1 / 20C discharge step), and optionally identifying the presence or absence of one or more markers associated with substantially complete and stable SEI formation on the hard carbon electrode in the recorded corresponding charge-discharge cycles or related analysis; optionally, if necessary, the polarization of the test cell is repeated one or more times at the same first current density until the presence and / or absence of one or more markers in the recorded corresponding charge-discharge cycles or related analysis are observed, and these markers are associated with substantially complete and stable SEI formation on the hard carbon electrode of the formed new test cell. Conventional thinking would suggest that a 1 / 20C rate would produce the best SEI for a particular test cell, although a 1 / 10C rate is also believed to form an acceptable SEI, thereby supporting acceptable cell performance. The method of the present invention may include the following steps:

[0124] The formed target battery is produced by repeating step a) on a target new battery (which is identical in chemistry, properties and composition to the new battery used in the first step) at a predetermined second current density, which is higher than the current density used in step a), wherein for a single discharge, the higher current density achieves the full discharge capacity of the battery in a time period of 5 hours or less, preferably 2 hours or less, preferably 1 hour or less, and more preferably 30 minutes or less, until one or more markers provide evidence of the formation of a substantially complete and stable improved SEI on the hard carbon working electrode.

[0125] The target cells are cells in which non-conventional formation steps are prepared / have been applied.

[0126] If necessary (and the marker, i.e., its presence or absence, indicates that it would be beneficial for further development of the SEI), the method may include further repeating the above-mentioned generation steps one or more times at the same second current density on the same formed target cell until one or more markers provide sufficient evidence of the formation of a substantially complete and stable improved SEI on the hard carbon working electrode.

[0127] It should be noted that improvements in the SEI formed on the hard carbon of the formed target cells are readily demonstrated where the formed target cells exhibit higher specific capacity and / or higher Coulombic efficiency during cycling at a nominal C-rate compared to the specific capacity and / or Coulombic efficiency exhibited by the formed test cells. It should be understood that the comparison at the nominal C-rate occurs in the formed cells where all other conditions are identical, e.g., the same number of polarization steps are applied to both. This ensures a direct performance comparison where the only difference is the particular high rate / current density formation conditions and the number of repeated polarization steps applied to the formed cells.

[0128] Forming the battery structure under optimal formation conditions

[0129] The present invention provides a battery formation method that forms an improved SEI on a hard carbon anode in a sodium ion electrochemical cell in a total time of 20 hours or less, preferably 5 hours or less, and more preferably 2.5 hours or less. After the improved SEI is formed, the battery will exhibit the described performance improvements during cycling at the nominal C rate of the particular battery.

[0130] In some embodiments, a set of optimized formation conditions (e.g., once determined according to the method of the first aspect described above) can be applied to a formation method applicable to the same new (original) battery or a batch of the same new (original) batteries, such as might be encountered in commercial battery manufacturing. The formation method comprises a first step:

[0131] - providing one or more new batteries to be formed based on sodium ion electrochemistry, said new batteries comprising:

[0132] o a counter electrode comprising an electrochemically oxidizable material capable of releasing sodium ions into a superconcentrated electrolyte in the cell during cell polarization, and

[0133] o a hard carbon working electrode for absorbing sodium metal ions received at the hard carbon working electrode from the super-concentrated electrolyte as reduced sodium stored in the hard carbon working electrode,

[0134] The super-concentrated sodium ion ionic liquid electrolyte comprises an ionic liquid and at least one sodium salt, wherein the sodium ion concentration is 75% or more of its saturation limit in the electrolyte.

[0135] The formation method then includes the step of producing a target cell having improved formation of a SEI on a working electrode of the formed target cell by applying the cell formation method to the new target cell.

[0136] polarizing the new target battery at a predetermined formation current density so that for a single discharge, the battery cut-off discharge potential limit and the final discharge capacity of the new target battery are achieved within 5 hours or less, preferably within 2 hours or less, preferably within 1 hour or less, and more preferably within 30 minutes or less; and

[0137] determining the presence and / or absence of one or more markers associated with the formation of a substantially complete and stable SEI on the hard carbon electrode during the recorded corresponding charge-discharge cycles or related analysis; and if necessary,

[0138] repeating the step of polarizing the resulting formed target cell one or more times at the same predetermined second current density or at different higher or lower predetermined formation current densities until the presence and / or absence of the one or more markers indicates that substantially complete and stable improved SEI formation has occurred on the hard carbon electrode of the target cell,

[0139] Wherein the improvement in the SEI formed on the hard carbon is demonstrated by the formed target cell exhibiting a higher specific capacity and / or a higher Coulombic efficiency during cycling at a nominal C rate compared to the specific capacity and / or Coulombic efficiency exhibited by the formed test cell. Preferably, (i) the predetermined formation current density and / or (ii) the number of polarization cycle repetitions corresponding to the number of polarization steps required to produce the improved SEI are determined by the method for determining optimized cell formation conditions described in the first aspect.

[0140] Suitably, the method of the present invention is carried out in a temperature range of 0°C to 100°C, preferably 20°C to 85°C, more preferably 25°C to 80°C, and even more preferably 45°C to 55°C. In some preferred embodiments, the method is carried out at 50°C (±2%). Preferably, the battery polarization involves constant current charging and discharging of the new test battery at a predetermined first current density within the full voltage window of the new test battery, which achieves the full discharge capacity of the battery within at least 10 hours of a single discharge, more preferably within at least 20 hours of a single discharge. Battery "charging" refers to the polarization of the battery so that ions are reduced (i.e., sodium or lithium, etc.) at the working electrode, while "discharging" is the reverse process of oxidation at the working electrode (i.e., desodiumization, delithiation, etc.).

[0141] In some embodiments, during polarization, the current density is selected so that for a single discharge, the cut-off discharge potential limit and the ultimate discharge capacity of the battery are reached in less than 5 hours, less than 2 hours, preferably 1 hour or less, more preferably 30 minutes or less. It should be understood that the desired formation time guides the level of current density used to achieve complete discharge in the above method.

[0142] In embodiments, the formation time refers to the time required to form a substantially complete, substantially stable improved SEI on the hard carbon working electrode, characterized in that the above-mentioned performance requirements of the battery are met. In short, in some embodiments, the substantially stable improved SEI is when the formed target battery exhibits a higher specific capacity and / or a higher Coulombic efficiency compared to the specific capacity and / or Coulombic efficiency exhibited by the formed test battery during cycling at the nominal C rate, and its integrity is sufficient to support higher performance. In some preferred embodiments, higher performance of the formed target battery compared to the test battery can be observed after up to at least 50 cycles, at least 100 cycles, at least 200 cycles, at least 500 cycles, at least 1000 cycles, at least 2000 cycles at the nominal C rate. The C rate is defined as the charge / discharge current divided by the nominal rated battery capacity. For example, when a battery with a rated capacity of 2,500mAh is discharged at 5,000mA, the discharge rate is 2C, so a full discharge will occur in 30 minutes. Likewise, a battery rated at 2,500mAh will have a 1C rate when discharged at 2,500mA, so it will be fully discharged in 1 hour. Likewise, a battery rated at 2,500mAh will have a 1 / 10C rate when discharged at 250mA, so full discharge will occur in 10 hours.

[0143] Desirably, the current density applied during the method is a constant current density.

[0144] Suitably, the hard carbon working electrode comprises, more preferably consists essentially of, hard carbon.

[0145] In some embodiments, for a single discharge step of the polarization cycle, the second current density reaches the cut-off discharge potential limit of the battery in 5 hours or less. In some embodiments, for a single discharge step of the polarization cycle, the second current density reaches the cut-off discharge potential limit of the battery in 2 hours or less.

[0146] In some embodiments, the first predetermined current density at the working electrode during the formation step of the test cell is 200 mA / g or less, 150 mA / g or less, 100 mA / g or less, 50 mA / g or less, 10 mA / g or less. In some embodiments, the first predetermined current density at the working electrode during the formation step of the test cell is about 50 mA / g to about 100 mA / g. In some embodiments, the second or third or higher current density at the working electrode in the formation step of the first target battery is about 350mA / g or more, about 375mA / g or more, about 400mA / g or more, about 450mA / g or more, about 500mA / g or more, about 550mA / g or more, about 600mA / g or more, about 650mA / g or more, about 700mA / g or more, about 750mA / g or more, about 800mA / g or more, about 850mA / g or more, about 900mA / g or more.

[0147] Specifically, for the ultra-concentrated ionic liquid based on C3mpyrFSI described in this embodiment, a current density of 30 mA / g is required for complete discharge at a 1 / 10C rate, a current density of 300 mA / g is required for a 1C rate, and a current density of 600 mA / g is required for a 2C rate.

[0148] Electrolytes based on "super concentrated" ionic liquids include sodium ion ionic liquid electrolytes, which are suitable for use in the battery of the present invention and are not particularly limited as long as the battery standards are met and they exist in liquid form at the operating temperature of the battery. Suitably, the electrolyte based on the "super concentrated" ionic liquid is dry in that it contains <50 ppm of water. The ionic liquid of the super concentrated electrolyte preferably comprises a pyrrolidinium cation, preferably an alkylated pyrrolidinium cation, preferably a 1-methyl-1-alkylpyrrolidinium cation (C3mpyr + ), most preferably 1-methyl-1-propylpyrrolidinium cation (C3mpyr + ). However, for the sodiation of hard carbons, the preferred electrolytes are superconcentrated ionic liquids based on C3mpyrFSI, in particular the electrolytes described in this example.

[0149] Otherwise, the sodium salt / ionic liquid electrolyte used according to the present invention may include a salt selected from 1-butyl-3-methylimidazolium hydrogen sulfate ([C4mim][HSO4]), 1-alkyl-3-methylimidazolium bromide ([C n mim][Br]), 1-hexadecyl-3-methylimidazolium chloride ([C 16mim][Cl]), 1-octyl-3-methylimidazolium chloride ([C8mim][Cl]), 1-butyl-3-methylimidazolium tetrafluoroborate ([C4mim][BF4]), 1-octyl-3-methylimidazolium tetrafluoroborate ([C8mim][BF4]), 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([C2mim][Tf2N]), 1-butyl- 3-Methylimidazolium chloride ([C4mim][Cl]), 1-hexyl-3-methylimidazolium tetrachloroferrate (III) ([C6mim][FeCl4]), 1-propyl-3-methylimidazolium iodide ([C3mim][I]), 1-ethyl-3-methyltristrifluoromethanesulfate ([C2mim][OTf]), 1-alkyl-3-methylimidazolium trifluoromethanesulfonate ([C n mim][Tf]), 1-ethyl-3-methylimidazolium acetate ([C2mim][OAc]), N-butyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)amide (([C4mPyr][Tf2N]) or ([C4mpy][Tf2N])), 1-ethyl-3-methylimidazolium tetrafluoroborate ([C2mim][BF4]), 1-dodecyl-3-methylimidazolium bromide ([C 12 mim][Br]), 1-octyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([C8mim][Tf2N]), 1-hexadecyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([C 16 mim][Tf2N]), 1-ethyl-3-methylimidazolium chloride ([C2mim][Cl]), 1-(3-aminopropyl)-3-methylimidazolium bromide ([(3-aminopropyl)mim][Br]), 1,2-dimethyl-3-butylimidazolium bis(trifluoromethanesulfonyl)amide ([C4(2-Ci)mim][Tf2N]), 1-butyl-3-methylimidazolium dicyanamide ([C4mim][N(CN)2]), 1-hexadecyl-3-methylimidazolium tetrafluoroborate ([C 16 mim][BF4]), 1-butyl-3-methylimidazolium hexafluorophosphate ([C4mim][PF6]), 1-butyl-3-methylimidazolium hexafluorophosphate ([C4mim][Tf2N]), 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide ([C4mpyr][Tf2N]), 1-butyl-3-methylimidazolium tetrachloroferrate (III) ([C4mim][FeCl4]), 1-ethyl-3-methylimidazolium bromide ([C2mim][Br]), 1-hexadecyl-3-methylimidazolium bromide ([C 16mim][Br]), 1,2-dimethyl-3-(3-hydroxypropyl)imidazolium bis(trifluoromethanesulfonyl)imide (C2-OH) N-ethyl-tri(2-(2-methoxyethoxy)ethyl)ethane ammonium bis(fluorosulfonyl)imide ([N 2(2O2O1)3 [FSI]) and N-ethyl-tris(2-(2-methoxyethoxy)ethyl)ethane ammonium bis(trifluoromethanesulfonyl)imide ([N 2(2P2O1)3 [TFSI]) in one or more organic salts.

[0150] In some embodiments, the sodium salt / ionic liquid electrolyte used in accordance with the present invention may include one or more organic salts, the organic salts including salts selected from bis(trifluoromethanesulfonyl)imide ([Tf2N] or [TFSI]), bis(fluorosulfonyl)imide ([FSI]), or combinations thereof.

[0151] For example, organic salts include 1-butyl (propyl) -1-methylpyrrolidine bis (trifluoromethylsulfonyl) imide ([C4C3mpyr][TFSI]) and N-methyl-N-propylpyrrolidine bis (fluorosulfonyl) imide ([C3mpyr][FSI]). Organic salts suitable for forming the electrolyte of the present invention may also include those disclosed in Energy Storage Materials Synthesized from Ionic Liquids by Gebrekidan Gebresilassie Eshetu, MichelArmand, Bruno Scrosati and Stefano Passerini (Ionic Liquids Angewandte Chemie Int. Ed. 2014, Vol. 53, p. 13342), the contents of which are incorporated herein in their entirety.

[0152] Desirably, the electrolyte includes a phosphorus-based organic salt. That is, the sodium ion ionic liquid electrolyte used according to the present invention may also include one or more organic salts selected from the phosphorus analogs of the organic salts disclosed herein. The phosphorus "analogs" of the organic salts disclosed herein refer to organic salts having the same chemical structure as the organic salts disclosed herein, but with phosphorus atoms replacing nitrogen atoms.

[0153] Therefore, the electrolyte used according to the present invention may include a group selected from trihexyl (tetradecyl) phosphonium bis (trifluoromethanesulfonyl) imide ([P 66614 [Tf2N]), trihexyl(tetradecyl)phosphoniumbis(fluorosulfonyl)imide ([P 66614 [FSI]), diethyl(methyl)(isobutyl)phosphonium bis(trifluoromethanesulfonyl)amide ([P 1224[Tf2N]), diethyl(methyl)(isobutyl)phosphoniumbis(fluoromethanesulfonyl)amide ([P 1224 [FSI]), triisobutyl (methyl) phosphonium bis (trifluoromethanesulfonyl) imide ([P 1224 [Tf2N]), triisobutyl(methyl)phosphoniumbis(fluoromethanesulfonyl)imide ([P 1444 [FSI]), triethyl (methyl) phosphonium bis (trifluoromethanesulfonyl) imide ([P 1222 [Tf2N]), triethyl(methyl)phosphoniumbis(fluoromethanesulfonyl)imide ([P 1222 [FSI]), trimethyl(isobutyl)phosphoniumbis(trifluoromethanesulfonyl)imide ([P 111i4 [Tf2N]) and trimethyl(isobutyl)phosphoniumbis(fluoromethanesulfonyl)imide ([P 111i4 ][FSI]) in one or more organic salts.

[0154] The electrolyte used according to the present invention may also include one or more organic salts selected from those described herein that introduce alkoxy ether functional groups into the side chains of the cations (eg, by substituting the alkyl chain on the cation).

[0155] In some embodiments, the electrolyte used according to the present invention includes one or more sodium salts selected from sodium bis(trifluoromethane)sulfonyl imide (Na[TFSI]), sodium bis(fluorosulfonyl)imide (Na[FSI]), sodium trifluoromethanesulfonate (NaOTf), sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), and sodium hexafluorophosphate (NaPF6).

[0156] Desirably, wherein the sodium ion is Na + , the electrolyte includes Na[TFSI] and [C3mpyr][TFSI], Na[TFSI] and [C4C3pyr][TFSI], Na[TFSI] and [C3mpyr][FSI], Na[TFSI] and [C4C3mpyr][FSI], Na[FSI] and [C3mpyr][TFSI], Na[FSI] and [C4C3mpyr][TFSI], Na[FSI] and [C3mpyr][FSI], Na[FSI] and [C4C3mpyr][FSI] or a combination thereof.

[0157] Desirably, the electrolyte includes sodium bis(fluorosulfonyl)imide (Na[FSI]) and N-propyl-N-methylpyrrolidinium bis(fluorosulfonyl)imide (C3mpyr[FSI]).

[0158] Other suitable ionic liquids include oxazolidine cations, such as [C1moxa] +、[C2moxa] + ; ammonium cations, such as [N 111,1O1 ], or ammonium with functional groups, such as ammonium cyanamide, morpholine; charge diffusion cations, such as hexamethylguanidine; pyrrolidinium cations, such as [C2epyr] + , [C (i3) mpyr]. These cations may be used with any suitable anion, but particularly TFSI - 、FSI - 、BF4 - or PF6 - Anions. Particularly preferred for the present invention are ionic liquids (ILs) having cations including HMG (hexamethylguanidinium), oxa (dimethyloxazolidinium, etc.) and ammonium (eg tetramethyl and methyl, triethyl, etc.), in particular FSI and TFSI.

[0159] According to the present invention, the sodium salt concentration in the electrolyte is not less than 75% of its saturation limit in the electrolyte. The sodium salt concentration in the electrolyte is the mole % of the sodium salt relative to the total mole of the sodium salt and the organic salt. "Saturation limit in the electrolyte" refers to the highest concentration of sodium salt in the electrolyte, at which sodium salt precipitation does not occur in the electrolyte at a given temperature. In other words, if the sodium salt further added to the electrolyte does not dissolve, the sodium salt concentration in the electrolyte at a given temperature is at its saturation limit. The saturation limit of sodium salt ions in the electrolyte at a reference temperature is a concentration that can be conveniently measured according to standard procedures known in the art. According to such a procedure, a gradually increasing amount of sodium salt is added to the organic salt at an initial temperature that is higher than the reference temperature for determining the saturation limit. Continue to add sodium salt until a visible undissolved salt precipitate is formed, indicating that the saturation limit is exceeded. The temperature is then reduced to the reference temperature, resulting in further precipitation of sodium salt from the organic salt. Once the sodium salt precipitation stops, the total amount of sodium salt precipitate is determined by separating the precipitate from the solution using means known to those skilled in the art. The sodium salt saturation limit at the reference temperature is calculated as the difference between the total sodium salt added to the organic salt and the amount of sodium salt precipitate.

[0160] "Not less than 75% of its saturation limit in the electrolyte" means that the sodium salt concentration is in the range of 75% to 100% of the saturation limit in the electrolyte. For example, if the saturation limit of the sodium salt in the electrolyte is 60 mol% at a given temperature, the sodium salt concentration in the electrolyte according to the present invention will not be less than 45 mol% (45 mol% is 75% of 60 mol%). In other words, in this example, the sodium salt concentration in the electrolyte according to the present invention will be in the range of 45 mol% to 60 mol%.

[0161] The saturation limit of the electrolyte is the saturation limit at the battery operating temperature. "Battery operating temperature" refers to the temperature at which the battery is put into use, for example, when the SEI layer is formed, during discharge to power an external load connected to the electrode, and / or during charging. In other words, at the battery operating temperature, the sodium salt concentration of the sodium salt / ionic liquid electrolyte is not less than 75% of its saturation limit in the electrolyte.

[0162] Preferably, the sodium salt concentration in the electrolyte based on the super concentrated ionic liquid is 80% or more, 85% or more, 90% or more, 95% or more or 100% of its saturation limit in the electrolyte. Preferably, the sodium salt concentration in the electrolyte based on the super concentrated ionic liquid is 40 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, 80 mol% or more, 90 mol% or more or 95 mol% or more. In some embodiments, the sodium salt concentration in the electrolyte is not less than 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% or 99% of its saturation limit in the electrolyte. In some embodiments, the concentration of sodium ions in the electrolyte is at its saturation limit.

[0163] In addition to being no less than 75% of its saturation limit in the electrolyte, in some embodiments, the sodium salt concentration in the electrolyte may also be 40 mol%, 50 mol%, or higher. For example, the molar concentration of the sodium salt in the electrolyte may be at least 40 mol%, 50 mol%, 55 mol%, 60 mol%, 65 mol%, 70 mol%, 80 mol%, or 90 mol%.

[0164] In some embodiments, the battery is in a half-cell configuration. For example, when the battery is in a half-cell configuration, the counter electrode is sodium metal, and the working electrode is a negative electrode material, such as hard carbon. In other embodiments, the battery is in a full-cell configuration. For example, the battery can be a full-cell configuration, and the counter electrode includes or consists of a material that can reversibly intercalate / deintercalate sodium ions within its atomic structure, absorb / desorb sodium ions through a reversible oxidation / reduction reaction, or promote an alloying / de-alloying reaction with sodium ions.

[0165] In some embodiments, the counter electrode comprises or consists of Na 0.45 Ni 0.22 Co 0.11 Mn 0.66 O2,Na 2 / 3 Fe 2 / 3 Mn 2 / 3 (O3), Na 2 / 3 Fe 2 / 3Mn 1 / 3 O2(P2), olivine-type NaFePO4, Na x FePO4, silicate, general formula is Nasicon type phase Na2M2(XO4)3 (M = transition metal and X = P, S).

[0166] In a preferred embodiment, the predetermined first current density of step a) achieves the full discharge capacity of the battery in 10 hours, corresponding to a conventional formation method, using a 1 / 10C rate for formation. In a preferred embodiment, the predetermined constant second higher current density of step b) achieves the full discharge capacity of the battery in 0.5 hours or less. In a preferred embodiment, the predetermined constant second higher current density of step b) achieves the full discharge capacity of the battery in 0.25 hours or less. When it is desired that the time period is 0.25 hours or 0.5 hours, it is most preferred to use a time period of 10 hours or less in step a).

[0167] Desirably, the nominal C rate of the formed target cell is 1 / 2C or 1 / 5C, although any particularly desired suitable nominal C rate may be used, as long as the same C rate is applied to the formed test cell of step a). Preferably, for the purpose of comparing performance with the formed test cell, the formed target cell may be further galvanostatically cycled at a lower C rate for up to 100 cycles, preferably up to 50 cycles.

[0168] Preferably, during nominal C-rate cycling (after SEI formation is complete), the target cell formed exhibits a Coulombic efficiency (CE) of 99.2% or greater, preferably 99.3% or greater, preferably 99.4% or greater, preferably 99.5% or greater, preferably 99.6% or greater, preferably 99.7% or greater, preferably 99.8% or greater, preferably 99.9% or greater, starting from the 20th cycle, more preferably starting from the 10th cycle, more preferably starting from the 6th cycle (in the case of 5 formation cycles). Preferably, the performance is compared to a test cell formed after 10 or more, 50 or more, or 100 or more cycles at the nominal selected C-rate of the cell. The higher the CE formed during cycling at the nominal C rate, the better, because as the battery ages, irreversible capacity loss or decay occurs, and small drops in CE away from unity accumulate as the battery cycles, so as the battery ages, the capacity decay that inevitably occurs in the late cycle will become earlier, with the starting CE closer to 99% rather than 100%. Therefore, given its higher CE during early nominal C rate cycling, the battery of the present invention will exhibit an overall longer cycle life (the number of cycles achievable) before reaching a definite end-of-life capacity loss point.

[0169] Desirably, one or more markers associated with substantially complete and stable SEI formation on a hard carbon electrode (e.g., in recorded corresponding charge-discharge cycles or related analysis) include:

[0170] (a) Discharge-charge curve markers / characteristics

[0171] - no significant electrolyte reduction voltage slope is observed during the recorded voltage-capacity cycles and / or a substantially static electrolyte reduction voltage slope is observed compared to the previous cycle, features indicating the progression of SEI development;

[0172] - observing the invariant features / stability of features in the recorded charge and discharge cycles by comparing the differences between a particular formation cycle and previous or subsequent formation cycles;

[0173] - the absence of "low voltage" features in the recorded charge and discharge cycles (e.g., below about 1.5 V after initial cycling of an exemplary half-cell) when comparing differences between a particular formation cycle and prior or subsequent formation cycles. Low voltage features are known / identifiable to one skilled in the art as being associated with electrolyte reduction / decomposition and / or electrolyte additive reduction / decomposition. These features can be determined by separate electrochemical studies of the particular electrolyte system used, such as by CV studies or the like, which can determine the redox peak voltages of the ionic liquid (cations and / or anions) and anions of the metal salt used or any additives included;

[0174] - the cut-off discharge potential limit of the cell is observed to be reached without the presence / absence of curve features associated with insertion of sodium ions into the negative active electrode (i.e., intercalation features), e.g., in the described half-cell example, sodium ion insertion is determined by the presence of a flat plateau around 0.01 V (i.e., the absence of an insertion peak in the curve during formation cycles, wherein an insertion peak is found in cycles once the formation of the modified SEI is substantially complete and substantially stable); and

[0175] -Observe minimal or stable irreversible capacity loss between cycles;

[0176] (b) Electrochemical impedance spectroscopy (EIS) markers / characteristics

[0177] - Evidence of low and / or stable EIS spans in electrochemical impedance studies, e.g. involving analysis of the recorded Nyquist plots. For example, for an unstable SEI, the EIS will show a significant increase in impedance and / or a decay in noise due to the lack of stability. A stable SEI will not reflect this behavior;

[0178] - Evidence of formation of a low-impedance SEI, e.g., caused by the magnitude of the EIS under load and the amount of polarization, i.e., the decrease or increase in relative potential under load for a full cell or symmetric cell under equivalent conditions (current, temperature, etc.);

[0179] - Evidence of a more ionically conductive SEI than formed in the test cells. For example, in the half-cell studies presented, Ohmic values ​​ranged from 10 to 100, indicating good transport of Na ions through the SEI and electrode interface.

[0180] (c) Differential volumetric analysis markers / signatures

[0181] - The absence of electrolyte reduction / decomposition and / or electrolyte additive reduction / decomposition peaks in the recorded differential capacity curve (dQ / dV). For example, the absence of FSI-anion reduction peaks in dQ / dV indicates the complete formation of the SEI layer in the half-cell embodiments described herein in the super-concentrated IL comprising a metal FSI salt;

[0182] - The absence of metal ion insertion peaks indicates that complete discharge occurs before metal ion insertion;

[0183] - At higher rates, Na + Ion adsorption / chemical adsorption peaks instead of Na appearing before the high-rate battery reaches full charge capacity + Insert peaks; and

[0184] - There is no intercalation peak, so after sufficient SEI formation, the intercalation peak becomes visible.

[0185] The detectable capacity difference of the sodium ion absorption step compared to the desorption step shows the charge consumed in the SEI formation during any particular polarization cycle. As the formation cycle progresses, the properties of the SEI continue to develop, such as composition, ionic conductivity, thickness, porosity, density, depending on the battery chemistry and electrolyte used. SEI formation is generally considered to be completed in a few formation cycles (e.g., 2 / 3 cycles) at traditional slow charge / discharge rates (1 / 10C or lower, 1 / 20C or lower), involving allowing the battery to be fully charged and fully discharged, which is considered to be critical for the optimal performance of the battery later. Therefore, less charge consumption as the cycle progresses indicates the degree of completeness of the SEI formation for any given cycle. As SEI formation progresses, the charge loss (irreversible capacity loss) from one formation cycle to the next will decrease as the SEI becomes more complete, more stable, and less additional electrolyte is consumed. Once the formed SEI is essentially complete and stable, that is, optimal SEI formation has occurred, the charge lost between the charge and discharge steps in consecutive polarization cycles is minimized because little additional electrolyte decomposition occurs at this stage. Thus, observing a reduction in irreversible capacity loss between adjacent cycles and / or minimal charge loss between charge and discharge steps can also be used to determine that a substantially complete and substantially stable SEI is formed after cycling.

[0186] During the first formation cycle performed on a new test cell, the method uses a current density low enough to achieve the full discharge capacity of the cell over a single discharge period of at least 10 hours, more preferably at least 20 hours. This means that the formation of the new test cell will be slow enough so that the SEI formation is also slow, and the cycle is naturally long enough to ensure that the formed SEI is substantially complete. Therefore, the analysis of the new test cell can identify the presence and / or absence of electrochemical analysis parameters / one or more markers associated with the formation of a substantially complete and substantially stable SEI of the slow formation step.

[0187] A "new cell" is a manufactured cell that has not been polarized and therefore includes pristine electrodes. Reference to one or more new cells in the various steps of the methods described herein means that new, unpolarized cells are used and that the cells are from the same batch of cells having the same chemistry, amount of active material, electrolyte type, etc., within experimental and manufacturing control limits.

[0188] For the first formation cycle performed on the target new cell, a current density is selected that is higher than the current density used for the test cell so that the cell cut-off discharge potential limit and the final discharge capacity of the target cell are reached in a single discharge of less than 5 hours, a single discharge of less than 2 hours, preferably a single discharge of 1 hour or less, and more preferably a single discharge of 30 minutes or less. Selecting a higher current density will cause the new target cell to reach the cut-off discharge potential limit faster than the same step of the test cell. For example, the higher current density used means that the cut-off discharge potential limit can be reached before sodium ion insertion occurs at the hard carbon electrode. Therefore, the preferred current density of the present cell is a current density that causes cut-off at a low discharge capacity. Therefore, the target cell will exhibit a reduced discharge capacity compared to the test cell.

[0189] On the other hand, the present invention relates to the use of a super-concentrated ionic liquid electrolyte in a method for forming a battery, wherein the formation method forms an improved SEI on a hard carbon negative electrode, preferably a hard carbon negative electrode in a sodium ion electrochemical cell, in 10 hours or less. The characteristics of the method and the super-concentrated ionic liquid electrolyte are as described above. Preferably, the use is in a method for forming a sodium ion electrochemical cell, using a super-concentrated electrolyte comprising an ionic liquid and at least one sodium salt, wherein the sodium ion concentration is 75% or more of its saturation limit in the electrolyte, the sodium ion electrochemical cell comprising a hard carbon working electrode, preferably a hard carbon working electrode, wherein the battery formation is completed at 50°C in 10 hours or less. Suitably, the use relates to a battery wherein the sodium ions are sodium ions, the hard carbon working electrode is hard carbon, and the electrolyte is [C3mpyr][FSI]IL having about 50 mol% NaFSI salt. In this case, approximately means ±2%.

[0190] definition

[0191] An "electrochemical cell" is a device that converts chemical potential energy into electrical energy.

[0192] "Half-cell" refers to a cell in a half-cell configuration, wherein the cell includes the working electrode and counter electrode under investigation, and is controlled by a potential. In a half-cell configuration, charge can only be extracted during discharge to a negative cell voltage. When in a half-cell configuration, the cell of the invention may be suitable for use as a diagnostic or testing device that can help measure the electrochemical properties of an electrolyte, or determine a suitable positive electrode for use in a full-cell configuration according to the invention.

[0193] "Full cell" refers to a battery in a full cell configuration, controlled by the cell voltage, such as a battery. In this configuration, the battery also includes a positive electrode material as a counter electrode and a negative electrode material as a working electrode. As used herein, the expression "full cell configuration" refers to a battery configuration in which the positive electrode and the negative electrode support a significant potential difference (e.g., greater than about 1V) after charging and charge can be extracted therefrom during discharge at a positive cell voltage. When the electrode pair is a pair of suitable negative and positive active material electrodes, the battery is a full cell configuration. When the electrode pair supports a high current density at the negative electrode and maintains a large number of polarizations or charge / discharge cycles, the electrode pair is suitable for use in a battery that can be used as a high-capacity and cycle-stable metal ion-based rechargeable battery.

[0194] “Intercalation” refers to the reversible insertion of the transport metal ion into the atomic structure of the electrode.

[0195] "Negative electrode" refers to the electrode from which electrons leave the battery during discharge (anode during discharge; cathode during charge). For example, when in electrical contact with a sodium ion ionic liquid electrolyte used in accordance with the present invention, the negative electrode material results in (i) the formation of an SEI layer due to undergoing at least one polarization cycle in which the electrolyte at the electrode is reduced to form an SEI. The negative electrode may include (or be made of) a hard carbon material that can reversibly embed sodium ions into its atomic structure, interact with sodium ions (e.g., absorb / desorb) by promoting reversible oxidation / reduction reactions, or promote alloying / dealloying reactions with sodium ions. Examples of materials that a hard carbon negative electrode may include (or be made of) include: hard carbon, graphite, activated hollow carbon, expanded graphite, hard carbon composites, and doped analogs thereof.

[0196] "Positive electrode" refers to the electrode into which electrons enter the battery during discharge (cathode during discharge; anode during charge). For example, the positive electrode may include (or be made of) a material that can reversibly intercalate sodium ions into its atomic structure, absorb / desorb sodium ions through a reversible oxidation / reduction reaction, or promote alloying / de-alloying reactions with sodium, as described herein.

[0197] "Sodium ion ionic liquid electrolyte" refers to an ionic liquid obtained by dissolving a sodium salt in an organic salt. In some embodiments, the sodium salt is a sodium salt equivalent of the organic salt (ie, they share the same anion).

[0198] "Polarization cycle" refers to the cycle of charging and discharging a battery. "Formation cycle" refers to the initial cycle or the first few (up to the first 5) polarization cycles within the life of the battery, which promote the formation of an SEI layer on the working electrode, negative electrode material or "anode". A battery that has undergone a "polarization cycle" means that the battery has undergone a two-step cycle, which includes: a step in which a certain density of current flows through the negative electrode in one direction; and a step in which the current is switched to flow through the negative electrode in the opposite direction. In some embodiments, the battery according to the present invention can be configured and used so that the current flows through the negative electrode in a cyclic manner in the opposite direction. That is, the battery may undergo multiple polarization cycles in which the current flows through the negative electrode in alternating opposite directions. As a result, potentials of alternating signs can be observed.

[0199] The skilled person will know the technical meaning of the expression "charge / discharge cycle", and how to perform such a procedure. For example, a charge / discharge cycle may be a charge / discharge performed after assembly to activate a rechargeable battery. As known to those skilled in the art, this refers to the procedure adopted to form the negative electrode by a charge / discharge procedure under controlled voltage, temperature and environmental conditions, the purpose of which is to induce the formation of a solid electrolyte interface (SEI) layer at the negative electrode. For the avoidance of doubt, in the context of the present invention, it is understood that one polarization cycle is equivalent to one charge / discharge cycle.

[0200] "Coulombic efficiency (CE)" is defined as the quotient of the discharge capacity under given operating conditions and its previous charge capacity. It is a measure of the reversibility of electrochemical energy storage reactions, and any value less than 1 indicates non-productive reactions, usually irreversible reactions. Any decrease in unit CE reflects many non-productive reactions per 1,000 reactions, which will lead to irreversible losses of reactants in each cycle, with huge consequences over hundreds of cycles.

[0201] “Irreversible capacity” is defined as the amount of charge lost between the discharged capacity and its previous charged capacity under a given set of operating conditions and reflects the magnitude of the irreversible processes that occur during polarization cycling.

[0202] The “cumulative irreversible capacity” is defined as the cumulative sum of irreversible capacities over multiple polarization cycles, which reflects the progress of irreversible processes in the battery.

[0203] DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0204] The present invention is described with reference to the following examples. It should be understood that the examples are illustrative and not limiting of the invention described herein.

[0205] The general application principle behind the present invention is demonstrated by the following half-cell studies involving high current density polarization (up to 5 formation cycles) of a pristine cell comprising a sodium metal counter electrode and a hard carbon working electrode in a superconcentrated IL, which is a 1:1 IL:Na salt, i.e., C3mpyrFSI IL with 50 mol% NaFSI salt. The SEI formed has the desired compositional characteristics described in the present disclosure.

[0206] Materials and methods

[0207] Electrolyte preparation and slurry casting

[0208] Hard carbon (HC) was purchased from Kuraray (Kuranode, SSA = 4m 2 / g). Na metal was purchased from Sigma-Aldrich. Battery grade sodium bis(fluorosulfonyl)imide (NaFSI, 99.7%) and N-methyl-N-propylpyrrolidine bis(fluorosulfonyl)imide (C3mpyrFSI, 99.9%) were purchased from Boron Molecular. Dimethyl carbonate (DMC, 99%) was purchased from Sigma-Aldrich and was used to clean the cycled electrodes. Before use, the electrolyte was vacuum dried by Schlenk line at 50 °C. Ultraconcentrated ionic liquid was prepared by dissolving 50 mol% NaFSI into C3mpyrFSI, stirring at 50 °C for 24 h, and then transferred to a glove box. The HC anode was prepared by mixing hard carbon, carboxymethyl cellulose (CMC, Sigma-Aldrich) and carbon black (Sigma-Aldrich) in a ratio of 8:1:1 with water as solvent. The slurry was then coated on the Al current collector using a spatula. The mass loading of the HC electrode was 1 mg / cm 2 .

[0209] Electrochemical measurements

[0210] The Na / HC cells were prepared in a glove box with O2 and H2O levels below 0.1 ppm. The R2032 half-cell was equipped with HC electrode (8 mm diameter) as the working electrode and Na metal (10 mm diameter) as the counter and reference electrodes. Polyethylene 5P09B (19 mm diameter, 38 μm thickness, 86% porosity) was used as a separator. The three-electrode cell was assembled in the same way in a custom device, with two separate sodium metals as counter and reference electrodes, respectively. Before testing, the assembled cell was left to stand at 50 °C for 24 h to wet. The Na / HC cells were cycled using a Neware battery cycler at different C rates (2C, 1C and 1 / 10C, ​​C = 300 mAh / g) in the voltage range of 0.01 to 2 V, and then tested for a long time at the same current density. EIS measurements were performed using a Biologic VMP potentiostat with a frequency range of 1 MHz to 100 mHz.

[0211] Material and electrode characteristics

[0212] Post-analysis characterization was performed by X-ray photoelectron spectroscopy (XPS) and solid-state nuclear magnetic resonance spectroscopy (NMR). XPS was performed on a Thermo Scientific Nexsa spectrometer equipped with a hemispheric analyzer. The incident radiation was 72W (6mA and 12kV, 400×800μm spot) of monochromatic Al Kα X-rays (1486.6eV). Survey (wide) and high-resolution (narrow) scans were recorded at analyzer pass energies of 150eV and 50eV, respectively. The survey scan had a step size of 1.0eV and a dwell time of 10ms. High-resolution scans were obtained with a step size of 0.1eV and a dwell time of 50ms. The base pressure in the analysis chamber was less than 5.0×10 - 9 mbar. A low-energy dual-beam (ion and electron) flood gun was used to compensate for surface charging. All data were processed using Casa XPS with energy calibration referenced to the low binding energy component of the C1s peak at 284.8 eV. Etch depths were based on Ta2O5 (0.30481 nm / s) and used as an approximation in all depth analyses. Solid-state magic angle spinning (MAS) NMR experiments were collected on a 500 MHz (11.7 T) Bruker Avance III wide-aperture spectrometer. Samples formed under different formation protocols were scraped from a cycled cathode in an argon glove box. Control samples immersed in IL electrolyte for 24 h were also prepared by the same procedure. The samples were then rinsed with DMC and dried under vacuum before being mixed with boron nitride as a filler material and then loaded into a 1.3 mm MAS NMR rotor. They were then spun at 40 kHz using dry air. 23 The Na spectra were acquired using single pulse experiments with a recycle delay of 0.5 s and 20,000 scans. 19 F spectra were acquired using a Hahn echo pulse sequence with a 50 μs echo delay, a 1 s recycle delay, and 20,000 scans. Both nuclei were referenced with solid NaF (23 Na is δ=7.4ppm, 19 F is -224.2ppm). All samples were packed in an argon environment.

[0213] Results and Discussion

[0214] Example 1 - Constant current charge-discharge SEI formation - capacity, cycle performance and coulombic efficiency

[0215] Galvanostatic charging and discharging of the cell (based on measuring the potential in a cell polarized at a constant current) reveals the irreversible capacity loss that occurs during SEI formation, while further illustrating SEI stability by considering the capacity retention upon cell cycling (e.g., at a subsequent nominal C-rate for a particular cell).

[0216] The initial SEI formation occurring at the hard carbon electrode due to the first sodiation process (occurring during the first formation cycle of the original cell in the half-cell configuration) can be determined by the presence of features related to the reduction / decomposition of electrolyte components, such as the voltage slope during the first charge step in full-cell measurements, but in the case of half-cell studies involving a sodium metal counter electrode, which is carried out during the first hard carbon sodiation step / discharge process. The voltage slope associated with the electrolyte reduction / decomposition caused by the electrolyte reaction is a useful marker for incomplete SEI formation. The presence of similar electrolyte decomposition / reduction voltage slopes in subsequent formation cycles indicates that the SEI for a particular cycle is incomplete or can provide information that the SEI is close to completion because the voltage slope shortens in successive sodiation cycles. Similarly, SEI formation / electrolyte reduction peaks can be observed in cyclic voltammetry experiments. Other markers include changes in the EIS during cycling, such as significant fluctuations and the generation of noise, which are also evident in the case of an incomplete and unstable SEI. In contrast, an essentially noise-free EIS during cycling indicates the formation of a stable and complete SEI. For example, an S / N ratio of 10 or less, preferably 5 or less, and most preferably 3 or less, indicates that the SEI is stable / intact.

[0217] Furthermore, the observation of minimal irreversible charge loss between successive charge and discharge steps can also be used to identify the cycles that lead to substantially complete and substantially stable formation of the SEI.

[0218] In proof-of-concept experiments, three different formation protocols (1 / 10C for test cells and 1C or 2C for target cells) were applied to a hard carbon working electrode for half-cell chemistry reactions within the full voltage window of the 0.01V sodiumation cutoff and 2V de-sodiumization process of the half-cell chemistry in a novel half-cell setup using sodium metal as the counter electrode. Various potential vs. time curves for the baseline (1 / 10C, ​​C=300mAh / g based on HC) and alternative formation protocols (1C and 2C) can be observed in Figure 1a. In this study, up to five formation cycles were used to observe the progression / establishment of a complete and stable SEI, although during higher current density processes, complete SEI formation occurred only after the first or second cycle. The conventional formation protocol uses the typically slower 1 / 10C current density step, with one complete formation cycle taking approximately 20 hours (the discharge step takes approximately 10 hours), and a total of approximately 95 hours to complete the five cycles required for the establishment of a complete and stable SEI in the 1 / 10C test cell (see Figure 1b). In contrast, the 1C and 2C formation protocols require only about 1 hour and about 0.5 hours per charge or discharge cycle, respectively, reducing the total formation time (needed to observe complete and stable SEI establishment at 1 / 10C) for 5 formation cycles for 1C and 2C cells to an extremely short 5 hours and 2.5 hours, respectively. This time would be even shorter if complete SEI formation occurred after only the first or second cycle.

[0219] As shown in the constant current charge / discharge curves of Figure 1c, for the first formation cycle involving the sodiation of the hard carbon in the original cell half-cell, the discharge curve shown by the traditional slow 1 / 10C formation test cell shows that a full discharge capacity of 313 mAh / g occurs at the cut-off sodiation voltage, with a reduction slope starting from around 0.75 V, followed by a long flat platform at around 0.01 V. A reduction platform between 0.85 V and 0.97 V can be observed in the first cycle at 1 / 10C (see Figure 1(f)), which disappears in the fifth cycle. The original slope of the discharge voltage of about 0.75 V is attributed to the formation of SEI on the hard carbon surface (i.e., electrolyte decomposition), and thus the long flat platform starting from around 0.01 V is attributed to the Na + Insertion of hard carbon graphite layers helps achieve high capacity at slow C rates (see Figures 1(c) and (f)). The 1 / 10C rate reflects the low current density used in traditional slow formation rates, where achieving full discharge capacity during polarization is expected to favor optimal SEI formation. CV cycling (see Figure 1(g)) shows that electrolyte decomposition produces a small reduction peak (about 0.73V) in the first cycle, but this reduction peak is not observed at the 5th cycle, indicating that SEI formation is mainly completed by the 5th cycle under 1 / 10C conditions. The broad reaction peak between 0.2V and 1V corresponds to the adsorption of Na clusters on carbon defects.

[0220] Interestingly, however, the sodiation reaction in the first formation cycle of the 1C target cell and the 2C target cell did not go to completion, as indicated by the short reaction slopes at the onset of 0.5 V and 0.35 V, respectively, where most of the capacity was contributed by electrolyte reduction (voltage slope indicative of SEI formation) and Na + Adsorption to the surface dominates, while no capacity increase from sodium insertion / intercalation is observed during the initial formation cycles of the 1 / 10C cells. As a result, the full discharge specific capacities achieved by the high-rate cells are very low, 121 mAh / g for 1C and 97 mAh / g for 2C, compared to 313 mAh / g for the 1 / 10C cells. Given the poor capacities observed, it is not expected that these cells will produce a useful SEI under these formation conditions.

[0221] Since the voltage slope of the 2C battery is shorter than that of the 1C battery, and again shorter than that of the 1 / 10C battery, this means that the electrolyte decomposition during the SEI formation of the 2C battery is minimal, while at both high current density conditions, less electrolyte decomposition occurs during the SEI formation compared to the same stage of the 1 / 10C battery. That is, less electrolyte is consumed during the SEI formation process. The amount of electrolyte loss corresponds to the irreversible capacity loss between the charge and discharge of the continuous cycle. In addition, the curve of the 5th cycle shows that the capacity loss between the charge and discharge curves is very small (see Figure 1(d)), which indicates that when the 5th cycle is completed in all batteries, the SEI formed is basically complete and basically stable at this stage.

[0222] The charge-discharge curves of the 6th cycle of the test battery formed at 1 / 10C and the target battery formed at 1C and 2C are shown in Figure 7 (a) and 7(b) ((b) is Figure 7 (a) is an enlarged view of a portion of (a). The curves for the 2C-formed target cell at the 6th formation cycle at 2C rate show that the sodiation and desodiation overpotentials are lower for the 2C sample compared to the other cells, whereby the potential is less negative during sodiation, equivalent to easier sodiation, and less positive during easier desodiation, compared to the previous (fifth) formation cycle, and compared to the 1C and 1 / 10C formation cell sixth cycle curves. This is due to the complete and stable SEI formation occurring at the 5th formation cycle. It is also interesting to note the presence of a long voltage plateau associated with sodium insertion / embedding into the hard carbon anode, meaning that the cell is accommodating and releasing more charge during this cycle.

[0223] Figure 1(d) clearly shows the later charge / discharge behavior of the three formed cells at a nominal C-rate of 1 / 2C after completing the considered formation protocol. Unexpectedly, the 2C cell has the highest discharge capacity of 242.5 mAh / g, followed by 237.0 mAh / g for the 1 / 10C cell and 216.8 mAh / g for the 1C cell. This suggests that high-rate induced SEI formation is beneficial for sodium storage as it has surprisingly good capacity storage, considering the formation speed and the harsh high current density conditions used.

[0224] Example 2 - Differential Capacity Analysis

[0225] Δ(Delta)dQ / dV analysis can provide a comprehensive understanding of the factors involved in SEI formation and Na + The peaks for intercalation / deintercalation are deconvoluted. Therefore, the SEI formation process at different formation C-rates can be distinguished. Two reduction peaks at 0.96 V and 0.87 V were observed in the initial cycle of the 1 / 10C cell (Figure 2f), which is due to the electrochemical reduction of FSI anions in the electrolyte caused by different coordination environments. Note that the reduction peak of the first cycle was not detected in all cells at the 5th cycle (Figure 2g-i), indicating that a complete and stable SEI has been established at this stage. When the C-rate is increased to 1C and 2C, the peak position shifts to lower (more negative) potentials during the first discharge process, 0.52 V for 1C cells and 0.45 V for 2C cells. These changes indicate that there are differences in the SEI formation mechanism due to the interfacial and mass transfer interactions occurring under these conditions.

[0226] Interestingly, when the current density increases from 1 / 10C to 1C and 2C, the peak amplitude decreases significantly and the peak shape becomes broader. This may be due to the large amount of charges approaching the carbon surface at low rates, most of which enter the low plateau region (0.01-0.1V), resulting in full capacity. The peak intensity is affected by the higher rate Na + The limitation of ion transport leads to a shorter relaxation time of phase equilibrium and causes uneven distribution of Na near the carbon surface. Therefore, the uneven distribution of sodium on the hard carbon surface leads to higher overpotential and broader redox peaks. At the same time, the electrolyte decomposition process of SEI layer formation and the corresponding SEI configuration are also affected, which will be discussed in the following section. Since the reduction peak of the first cycle was not detected in the subsequent cycles (Figure 2(d)-(i), Figure 2(j)-(q)), this indicates that SEI formation has been established in the first cycle. The two large peaks at 0.6 V in Figure 2(g)-(h) are attributed to Na + The adsorption / chemisorption of ions on the active sites of carbon materials is different from the insertion peak in Figure 2(i), where most of the capacity comes from the diffusion contribution.

[0227] Example 3 - Coulombic Efficiency

[0228] All formed cells with complete and stable SEI formation (after 5 cycles) were then cycled at the same selected cell nominal C-rate (1 / 2C and 1 / 5C) for further evaluation after completing 5 formation cycles.

[0229] In such cycles, the formed batteries exhibited obvious capacity changes at 1 / 2C (Figures 3(a), (c), (d) and (g), and the specific capacities at the 40th cycle were 258 mAh / g at 2C, 250 mAh / g at 1C and 240 mAh / g at 1 / 10C, ​​respectively (see Figure 3(b)). It is worth noting that the capacity increment trend of all Na / HC batteries at 1 / 2C current density is believed to be due to the wettability of the hard carbon material by the high-concentration electrolyte at high rates, which is related to the concentration gradient. The long-term charging capacity of the three batteries in Figure 3 follows the same trend. The 2C battery has the highest charge capacity, and the 1 / 10C battery has the lowest charge capacity. The Coulombic efficiency (CE) of the three batteries in Figures 3(b) and (h) is consistent with the cycling data, where the 1 / 10C battery shows the lowest Coulombic efficiency during cycling, averaging 99.0%, while the 1C and 2C batteries have higher Coulombic efficiencies, both close to 99.6%. This may be related to the reconstruction of the SEI formed by 1 / 10C, ​​which will lead to the formation of more irreversible electrochemical byproducts. The lower Coulombic efficiency of the 1 / 10C battery will, to a certain extent, lead to faster capacity decay and have an adverse effect on the overall battery performance.

[0230] The excellent Coulombic efficiency of 99.6% for the target cells formed at 1C and 2C is believed to be related to the formation of a strong, substantially complete and substantially stable SEI layer on the carbon surface by the fifth formation cycle at high C rate, which is substantially uniform and more ionically conductive than that of the 1 / 10C test cell, and thus promotes Na + Diffusion through the SEI. The stability of the SEI after 5 cycles can also be observed from the EIS studies.

[0231] Figure 2b is an inset of Figure 2a, where electrolyte decomposition occurs during the first cycle when the SEI is initially formed. The three arrows in (b) point out the very small and difficult to observe reduction plateau in these curves. Therefore, this feature can be more clearly demonstrated by considering the corresponding dQ / dV curves in Figure 2d-e), which are consistent with the reduction peaks in the insets of Figure 2d-f (0.45V, 0.52V and 0.96V, respectively), clearly indicating the electrolyte decomposition peak.

[0232] In addition, Figure 2c shows that the Na +insertion plateau, while the 1C and 2C target cells do not show the same insertion plateau. This is because the high current used results in a larger polarization associated with the ohmic resistance, so the time required for the cell to reach the cutoff potential is shorter than that of the 1 / 10C cell, so the insertion reaction is not complete. This is why the 1C and 2C cells have much lower capacity than the 1 / 10C cell during the formation cycle. The SEI is formed in the region between 1V–0.5V because it is through this region that the SEI is formed. It is worth noting that from Figures 3a and b, it can be seen that the capacity observed over five formation cycles does not affect the long-term capacity. In contrast, the 2C has a better capacity because the SEI formed between 1V–0.5V is more complete and more ionically conductive, thereby enhancing the Na + Reaction kinetics.

[0233] Figure 3e summarizes the cumulative irreversible capacities of the three batteries. The 1 / 10C battery has the highest irreversible capacity of 59 mAh / g in the first cycle, while the 1C battery has 38 mAh / g and the 2C battery has 36 mAh / g, which means that the faster rate battery consumes less electrolyte. This is confirmed by the reduction plateau of the 1 / 10C battery at 0.75 V, which is related to the decomposition of a large amount of electrolyte. The high cumulative irreversible capacity of the 1 / 10C battery can be observed in the continuous formation cycle (insert picture in Figure 3e), while the values ​​of the three batteries become negligible when the current density becomes 1 / 2C. Figure 3(f) shows the cycling stability of the 2C formation battery at a current density of 1 / 2C for more than 300 cycles. The battery shows a high reversible capacity of 259 mAh / g after 300 cycles, with a capacity retention rate of 99.7%. The charge and discharge curves of the 50th and 300th cycles in Figure 3(i) show that the capacity difference between the two cycles is negligible, which is consistent with the stable cycling performance. The impact of rapid protocol formation on rate performance testing can also be seen in Figure 8 (c) and (d), where the 2C battery has a higher specific capacity of 260 mAh / g when the current density is reduced from 2C to 1 / 10C. At low current density, the 2C battery maintains its advantage over the 1 / 10C battery, with an average capacity increase of 8 mAh / g and 6 mAh / g at 1 / 5C and 1 / 2C, respectively. However, when a 1 / 5C current density is applied (Figure 3g), all batteries show a fairly high capacity (280 ± 2 mAh / g), while the charge capacity in Figure 3d is significantly higher due to the irreversible Na +intercalation and has a relatively low value (275±2mAh / g). At the same time, the coulombic efficiency shows a similar value of 98.5±0.2% in Figure 3h, which indicates that the battery performance is not reduced by the rapid formation of C rate. Higher C rates of 3C and 10C were also examined on the Na / HC battery (Figure 3(j)) for comparison with the formation of 2C. When the current density was changed to 1 / 2C, the 10C battery recovered slowly, with the capacity increasing from 77.8mAh / g to 216.7mAh / g from the 6th cycle to the 50th cycle. Interestingly, the capacity of the 2C and 3C batteries increased rapidly to 260mAh / g and 250mAh / g, respectively, at the 20th cycle. This can be explained by the formation of 10C on the carbon surface, which produces an unfavorable SEI, which is not conducive to Na + diffusion, and therefore the capacity is lower than that of the 2C formed cell. The inset shows that between the 20th and 40th cycles, the average capacity increment from the 3C cell to the 2C cell is 6 mAh / g. Here, under the current conditions, the inventors conclude that the 2C pretreatment is the optimized formation protocol in the HC sodium-ion half-cell when a highly concentrated ionic liquid electrolyte is used. Obviously, the optimized formation protocol described in this article does not limit the cell performance, and unexpectedly on the contrary, at a certain current density, the cell after the fast C rate exhibits better performance than the conventionally formed cell, and the formation time of Na / HC in the ultra-concentrated ionic liquid electrolyte can be reduced by 38 times.

[0234] Example 4 - Electrochemical Impedance Spectroscopy

[0235] In order to correlate the formation protocol with the interfacial properties of the carbon surface, EIS (Electrochemical Impedance Spectroscopy) measurements were performed. A three-electrode setup was designed with a Na foil as the counter electrode, a Na roll as the reference electrode, and hard carbon as the working electrode. Thus, Na metal acted as both the reference and counter electrode in the EIS experiment. The purpose of the three-electrode EIS measurement was to exclude the influence of the Na counter electrode on the interfacial properties. Figure 4 The Nyquist plots in (a)-(c) show the various EIS resistances of the three formed batteries after the 1st, 2nd, and 5th cycles, which clearly show that the 2C battery has the lowest resistance, while the 1 / 10C battery has the highest resistance. The curves are further fitted into three components using an equivalent circuit, and the results are shown in Figure 4 (d)-(f), Table 1 and Fig.10 The preferred SEI / HC electrode has an R of less than 500 ohms, preferably 300 ohms or less, more preferably 200 ohms or less after the first formation cycle, the second formation cycle, the third formation cycle, the fourth formation cycle, or the fifth formation cycle. intParticularly preferred SEI / HC electrodes have an R of 100 ohms or less, more preferably 75 ohms or less, after the first formation cycle, the second formation cycle, the third formation cycle, the fourth formation cycle, or the fifth formation cycle. int In some cases, after more than one formation cycle at, for example, 2°C, R int Can be less than 50 ohms. R int This can be determined by the EIS set up as described above.

[0236] Table 1. Summary of fitted EIS data for the 3 formed cells at the 1st, 2nd and 5th cycles

[0237]

[0238] Ohmic resistance comes from the entire battery including electrolyte and current collector. The semicircle in the high frequency area represents Na + The interfacial resistance when diffusing through the SEI layer. The mid-frequency semicircle is the charge transfer resistance, which is due to Na + Diffusion into the HC body caused.

[0239] The 2C formation cell exhibited the lowest resistance, 45 ohms, while the 1C formation cell had a resistance of 300 ohms, and the 1 / 10C formation cell exhibited the highest resistance, 700 ohms. During the five formation cycles, both the interfacial resistance and charge transfer resistance of the 2C cell showed a stable trend. The interfacial resistance of the 2C cell (optimized formation protocol) was significantly lower than that of the 1 / 10C cell, indicating that a robust and highly ionically conductive SEI was formed under 2C conditions. This can be explained by the complete decomposition of the electrolyte and SEI formation occurring in the 1 / 10C formation cell after the first cycle, thereby forming a thick SEI layer, resulting in a longer Na + diffusion pathway, thus explaining the higher resistance observed. In contrast, the SEI formation process of the 2C cell is very fast, thus achieving an SEI layer of different composition with higher ionic conductivity. The SEI in the 2C cell favors Na + diffusion at the electrode / electrolyte interface and would reduce the activation energy. Figure 4 The decrease in interfacial resistance of the 1 / 10C battery in (f) after 5 cycles is due to the incomplete SEI formation and the greater consumption of electrolyte in the traditional formation process, which is also the reason for the Na + The reason for the slow diffusion kinetics.

[0240] Example 5 - XPS and etching studies

[0241] XPS tests were performed to analyze the composition of the SEI formed on the HC anode under different formation protocols. The C1s spectra in Figures 5a and 5d show that the three HC electrodes are covered with CN (402 eV) and C=O (288.3 eV) species in the decomposed ionic liquid; while less CN species were found in the 1 / 10C battery compared to the 1C and 2C batteries (Figures 5(f)-(h)). The CN peak disappeared after etching for 2 minutes, indicating that the CN-containing species of the SEI are located in the outer layer. Interestingly, the CN peak is almost unobservable for the 1 / 10C formed electrode.

[0242] The N1s spectrum in Figure 5(b) is consistent with the C1s spectrum, indicating that it comes from C3mpyr + N + (402.8eV) exists in the outer layer of SEI and can be + After etching, it is removed (Figure 6(f) and 6(g)). In addition to C3mpyr + In addition, two main peaks corresponding to NS=O (398 eV) and N=SO (399.8 eV) were found in the SEI layer, which originated from FSI-decomposition. Interestingly, an additional peak at 396 eV was observed in the 1 / 10C cell, which was attributed to atomic nitrogen, even in the presence of Ar. + This peak can still be obtained after cluster etching for 40 minutes. From the etching profile in Figure 6(f), it can be detected that atomic nitrogen exists in the entire SEI layer. The S2p high-resolution spectrum in Figure 5(c) shows that –SO2F- (168.6 eV) and -SO x -(166.3 eV), and a “small” sulfur-containing species at 164 eV (164–160 eV) below (inset in Figure 5(c)) distinguish the 1 / 10C hard carbon from its 1C and 2C counterparts. Another inorganic SEI composition for all three cells is Na2O, as shown in Figure 5(e). Although these inorganic species are reported to be + Has a lower diffusion energy barrier, thus increasing the Na + However, the presence of more reduced sulfur species in the SEI of the 1 / 10C formed cell makes the SEI layer thicker, thereby increasing the Na + diffusion pathways and reduces the reaction kinetics.

[0243] The etch depth profiles in Figure 6(a)-(d) allow us to clearly understand the SEI composition originating from the three different formation protocols considered. Within the first 6 minutes of etching, the content of sulfur (S), fluorine (F), oxygen (O), and nitrogen (N) increases continuously, while the carbon content decreases significantly for all three systems. This is due to the presence of Na2O, Na2SO x / NaNSO2F, NaF and other inorganic substances. It is worth noting that the ratio of C and O in the 2C formed HC electrode exceeds 1 after 40 minutes of etching (Figure 6(a)), which is the same trend as the original electrode (Figure 6(d)), indicating that the surface of the 2C hard carbon is getting closer and closer to the bulk surface after 40 minutes of etching. In contrast, the C / O ratio of the 1 / 10C electrode is less than 1, indicating that there are more Na2O substances in the inner layer of the SEI, thus contributing to the formation of a thicker SEI layer. The C / O ratio of the 1C hard carbon (Figure 6(b)) is between that of the 2C and 1 / 10C batteries, following the same trend that the SEI thickness plays an important role in the capacity and EIS resistance. The schematic diagram in Figure 6(e) shows the differences in the SEI composition of the three formation treatments: During the 2C formation process, a thin SEI layer is quickly formed on the hard carbon surface with a shorter Na + In contrast, the 1 / 10C battery experienced more extensive electrolyte decomposition, resulting in more inorganic species and a small amount of sulfur and atomic nitrogen in the SEI composition, so the SEI was much thicker than that in the 1C and 2C batteries, which hindered the Na + Diffused into the carbon interlayer, it has lower ionic conductivity. The inventors’ previous work showed that the impact of SEI formation in lithium and sodium batteries varies depending on electrolyte polarity, electrolyte concentration, and pretreatment protocol. In particular, MD simulation results concluded that under high-rate pretreatment, the inner layer of the anode builds a higher concentration of Na x FSI y Aggregates, forming an inorganic-rich SEI that is beneficial to battery cycling. x FSI y Aggregates with low concentrations but high amounts of C3mpyr + Cation. C3mpyr + The involvement of cation decomposition produces a thick and organic-dominated SEI layer.

[0244] The C / O ratio on the 2C hard carbon is consistent with that of the original electrode (Figure 6d), which indicates that the etched surface on the 2C-formed cell hard carbon is getting closer to the bulk surface. However, the opposite C / O ratio (greater than 1) of the 1 / 10C-formed cell electrode has a thicker SEI layer, which indicates that this is the result of the 40 min Ar + The reason why etching has not reached the bottom of SEI.

[0245] The C / O ratio of the hard carbon formed in the 1C cell (Figure 6b) is between that of the 2C and 1 / 10C cells, following the capacity and EIS resistance trends discussed above.

[0246] It can be concluded that under high current formation treatment, a thinner or more ionically conductive SEI layer is gradually formed on the carbon surface, where the SEI has the characteristics of a shorter Na+ diffusion path and stronger ion conductivity. + The diffusion paths may be the result of a thinner, or more porous or less dense SEI, or a combination of one or more of these factors, which overall result in shorter ion diffusion paths. This is a surprising finding because the traditional idea of ​​SEI formation from organic electrolytes suggests that a thick and comprehensive SEI layer is needed to ensure optimal battery performance. The current results are completely opposite, using ultra-concentrated ionic liquid electrolytes at high current rates and fast formation times to form a better SEI with improved ionic conductivity / shorter ion diffusion paths (thinner, or less dense, or more porous, or all of these characteristics, etc.), which helps improve battery performance while consuming less electrolyte in SEI formation.

[0247] XPS studies support that the 1 / 10C cells undergo extensive electrolyte decomposition (consistent with the cycling signature showing more irreversible capacity loss from SEI formation in the 1 / 10C cells), with more sulfur and atomic nitrogen produced in the SEI components, and thus the SEI is believed to be thicker and less porous or more dense than the more ionically conductive SEIs of the 1C and 2C cells. The 1 / 10C SEI impedes Na + Diffusion into the carbon graphite layer due to its poor ionic conductivity characteristics. In addition, as mentioned earlier, the higher degree of electrolyte decomposition that occurs during the formation of 1 / 10C cells will ultimately lead to faster capacity decay in the long run due to the resulting electrolyte shortage.

[0248] Example 6 - Cumulative irreversible capacity and number of cycles

[0249] Figure 8(a) is a graph of irreversible capacity (mAh / g) versus cycle number for the first 1 to 10 polarization cycles (including the first 5 formation cycles) for a 1 / 10C test cell and 1C and 2C target cells. The irreversible capacity data show that the irreversible capacity loss in the 1C and 2C formation cells (cycles 1 to 5) is much less, and thereafter (cycles 6 to 10) after the necessary substantially complete and stable SEI is formed, further irreversible capacity loss is very low and very similar for each cell in cycles 6 to 10). The data indicates that for cells formed according to the formation method of the present invention, less charge enters SEI formation during each formation cycle compared to the corresponding cycle of a test cell formed using a current density consistent with conventional low current densities used in commercial formation protocols. The fact that less charge is transferred to SEI formation indicates that the SEI formed in cycles 1 to 5 of the target cell is different and / or improved compared to the test cell. It is believed that the difference / improvement may be one or more of the following: a more ionically conductive SEI (with respect to sodium ion transport); or a thinner SEI that is more ionically conductive and / or porous and / or less dense and / or has lower impedance and / or has greater stability; or a SEI of similar thickness that is more ionically conductive and / or porous and / or less dense and / or has lower impedance and / or has greater stability, or a combination of one or more of these factors, which generally results in shorter ion diffusion paths. A further key feature of the SEI formed by the formation method proposed by the present invention is the subsequent stability of the SEI in maintaining low impedance (after the necessary formation cycles are completed), and continued charge transfer during subsequent cycles at the nominal C rate of the battery.

[0250] Fig. 9 The cumulative irreversible capacity for the first 5 formation cycles is shown, indicating that the 1 / 10C formation test cell has the largest irreversible capacity of all 3 cells, which may be related to the extensive electrolyte decomposition associated with the formation of a thick or dense SEI layer. In contrast, the 2C and 1C cells show much less cumulative irreversible capacity, indicating much less overall electrolyte decomposition and suggesting that the formed SEI has a shorter Na + Diffusion paths, having one or more of the above characteristics (thinner, less dense, more porous, etc.).

[0251] When the cells were cycled at the same lower current density after formation, the cells formed at 2C showed the highest cumulative irreversible capacity in the 6th to 10th cycles, which may be due to the continued SEI formation. Regardless, after 25 cycles, the formation test cells starting from 1 / 10C showed the highest cumulative irreversible capacity of 70 mAh / g, indicating that the SEI formed and its properties during high current density formation have a profound effect on long-term cycling compared to the low current density formation test cells, so the formation target cells have better capacity utilization.

[0252] Example 7 - NMR studies

[0253] To further investigate the interfacial properties of HC electrodes under different formation protocols, solid-state 23Na and 19F MAS nuclear magnetic resonance (NMR) measurements were performed. All electrodes were cycled in superconcentrated ionic liquid electrolytes at different C rates (i.e., 1 / 10C, ​​1C, and 2C). A control sample soaked in electrolyte (denoted as soaked HC) was also included. Fig.11 All spectra in a are normalized to the electrolyte residual signal of 23Na, Fig.11 All spectra in b are normalized to the electrolyte residual signal (S–F) of the 19F spectrum. This is because it is difficult to quantitatively measure sample amounts due to the very small quantities involved and the addition of boron nitride filler material to the small sample rotor. Fig.11 In a, an IL residual signal at -8.9 ppm was observed for all electrodes, indicating that the IL residues are not easily washed away by organic solvents. However, we did observe another peak at +9.2 ppm for the three formed electrodes, while this signal was not seen for the soaked HC. According to the literature, this peak is attributed to NaF, which comes from the electrolyte decomposition product. Interestingly, although we normalized the spectra with the ILs residues, we found that the signal-to-noise ratio was very low for the 2C sample, while the signal-to-noise ratio was the highest for 1 / 10C. This proves that the content of SEI material on the 2C electrode is low, which is consistent with the results of EIS and XPS. The 19F MAS spectrum was also tested to further explore the SEI composition. Fig.11 There are three fluorine peaks in (b), which are attributed to SF groups in the electrolyte residue, CF groups in the MAS rotor material (i.e., background signals not generated by the sample), and NaF peaks in the electrolyte decomposition. The NaF peaks again appear only in the three formed electrodes, not in the soaked HC. At the same time, the S / N ratio of the 2C battery is the lowest, which is consistent with the 23Na spectrum.

[0254] in conclusion

[0255] The inventors have developed an optimized formation protocol for hard carbon anodes for sodium-ion batteries when using ultra-concentrated IL electrolytes. By adjusting the current density within a fixed potential range, the total formation time can be shortened by 38 times while still maintaining electrochemical performance. When cycled at 1 / 2C in long-term tests, the battery at high rate (2C, C=300mAh / g) is even better than the battery formed at a low rate. Comprehensive analysis of the SEI layer by three-electrode EIS, XPS and NMR techniques showed that our optimized formation protocol developed a thinner and more ionically conductive SEI structure. The interfacial resistance in the EIS test of the high-rate formation battery also confirmed the diffusion kinetics that promote Na+ through the SEI layer, which is a result of the formation of a highly ion-conductive SEI layer.

[0256] In summary, three formation protocols for NIB hard carbon anodes in superconcentrated ionic liquid electrolytes were investigated. In contrast to the established methods for carbonate-based solvents [6,41], the high current density 2C formation protocol produced the highest specific capacity during subsequent cycling at 1 / 2C current density, as well as the lowest EIS resistance, compared to the 1C and 1 / 10C formation protocols. Variable cycling conditions (e.g., long-term cycling at 1 / 5C) were not affected by the high C-rate treatment, indicating the necessity of applying high-rate formation protocols to regulate these electrolytes. XPS and NMR analyses revealed that a thinner SEI layer was formed after high C-rate formation, which could promote Na + Charge transfer and diffusion across the electrolyte / electrode boundary. Small but significant differences in SEI composition (absence of reduced S and N species after high-rate formation) may also contribute to the improved performance of the 2C sample. The optimized formation protocol outperforms the conventional low-rate formation protocol in Na-ion batteries. This new formation protocol may have a significant impact on industrial applications by reducing formation time and manufacturing costs, enabling the use of alternative safe electrolyte materials (e.g., ionic liquids ILs).

Claims

1. An electrochemical cell comprising: An ionic liquid electrolyte containing a super-concentrated sodium salt, comprising at least one ionic liquid and at least one sodium salt, wherein the concentration of the sodium salt in the super-concentrated sodium salt / ionic liquid electrolyte is 75% or more of its saturation limit in the electrolyte; a counter electrode or positive electrode comprising an electrochemically oxidizable material that releases sodium ions from the material into a superconcentrated electrolyte in the cell during a sodiation step or a charging step, and a hard carbon working electrode or negative electrode which absorbs sodium ions received from the superconcentrated electrolyte at the hard carbon negative electrode during the sodiation step or charging step as reduced sodium stored in the hard carbon, and, in, (a) The hard carbon negative electrode includes a formed solid electrolyte interface (SEI), wherein the solid electrolyte interface is: - Essentially free of low-order / short-range sulfur (S8 2- To S 2- ) substances, for example, as determined by XPS testing and etching studies; and optionally - substantially free of nitrogen atoms, as determined, for example, by XPS testing and etching studies; and / or (b) After the first formation cycle, the solid electrolyte interface (SEI) / hard carbon electrode has a bond with SEI (R int )-related interfacial resistance, as determined by electrochemical impedance spectroscopy.

2. The electrochemical cell according to claim 1, wherein The formed SEI is generated by reducing the electrolyte on the hard carbon electrode by polarizing the corresponding pristine cell at a high constant current density ranging from 1 / 2C to 5C for up to 5 formation cycles within the full voltage window of the cell.

3. The electrochemical cell according to claim 1 or claim 2, wherein: The formed SEI was generated by reducing the electrolyte on the hard carbon electrode by polarizing the corresponding pristine cell at a current density of 2C for up to 2 formation cycles within the full voltage window of the cell.

4. An electrochemical cell according to any one of the preceding claims, wherein The composition of the SEI has one or more of the following: - an outer layer comprising more CN material than the SEI of the formed test cell, as indicated by XPS testing and / or etching studies; - having a composition including a ratio of C to O of 1 or more after 40 minutes of etching, which reflects the original hard carbon after 40 minutes of Ar+ cluster etching.

5. An electrochemical cell according to any one of the preceding claims, wherein After completion of the SEI formation cycle, the battery exhibits a coulombic efficiency (CE) of 99.2% or more, preferably 99.3% or more, preferably 99.4% or more, preferably 99.5% or more, preferably 99.6% or more, preferably 99.7% or more, preferably 99.8% or more, preferably 99.9% or more during nominal C-rate cycling using a C-rate of 1 / 2C or slower.

6. An electrochemical cell according to any one of the preceding claims, wherein: Super-concentrated ionic liquid electrolytes include FSI - Anion or TFSI - The anion is preferably derived from one or more of an ionic liquid anion and a sodium salt anion.

7. An electrochemical cell according to any one of the preceding claims, wherein: The ionic liquid of the super concentrated electrolyte comprises a pyrrolidinium cation, preferably an alkylated pyrrolidinium cation, preferably a 1-methyl-1-alkylpyrrolidinium cation (C3mpyr + ), most preferably 1-methyl-1-propylpyrrolidinium cation (C3mpyr + ).

8. An electrochemical cell according to any one of the preceding claims, wherein: The electrolyte includes Na[TFSI] and [C3mpyr][TFSI], Na[TFSI] and [C4C3pyr][TFSI], Na[TFSI] and [C3mpyr][FSI], Na[TFSI] and [C4C3mpyr][FSI], Na[FSI] and [C3mpyr][TFSI], Na[FSI] and [C4C3mpyr][TFSI], Na[FSI] and [C3mpyr][FSI], Na[FSI] and [C4C3mpyr][FSI], or a combination thereof.

9. An electrochemical cell according to any one of the preceding claims, wherein: The electrolyte is a [C3mpyr][FSI] ionic liquid or a [C3mpyr][TFSI] ionic liquid having at least about 50 mol % of NaFSI salt.

10. An electrochemical cell according to any one of the preceding claims, wherein: The super-concentrated electrolyte and the formed SEI are free of carbonate species.

11. An electrochemical cell according to any one of the preceding claims, wherein: The battery is a full-cell configuration, and the counter electrode includes or consists of a material that can reversibly intercalate / deintercalate sodium ions within its atomic structure, absorb / desorb sodium ions through a reversible oxidation / reduction reaction, or promote an alloying / de-alloying reaction with sodium ions.

12. An electrochemical cell according to any one of the preceding claims, wherein: The counter electrode or positive electrode comprises or consists of: Na 0.45 Ni 0.22 Co 0.11 Mn 0.66 O2,Na 2 / 3 Fe 2 / 3 Mn 2 / 3 (O3), Na 2 / 3 Fe 2 / 3 Mn 1 / 3 O2(P2), olivine-type NaFePO4, Na x FePO4, silicates or Nasicon-type phases of the general formula Na2M2(XO4)3 (M = transition metal and X = P, S).

13. Use of a super concentrated ionic liquid electrolyte in a battery, wherein the concentration of sodium salt in the super concentrated ionic liquid electrolyte is 75% or more of its saturation limit in the electrolyte, and the battery comprises a hard carbon working electrode or a negative electrode to form a SEI on the hard carbon electrode, wherein: (a) The hard carbon negative electrode includes a formed solid electrolyte interface (SEI), wherein the solid electrolyte interface is: - Essentially free of low-order / short-range sulfur (S8 2- To S 2- ) substances, for example, as determined by XPS testing and etching studies; and optionally - substantially free of nitrogen atoms, as determined, for example, by XPS testing and etching studies; and / or (b) After the first formation cycle, the solid electrolyte interface (SEI) / hard carbon electrode has a 200 ohm or less bond with the SEI (R int )-related interfacial resistance, as determined by electrochemical impedance spectroscopy.

14. The use according to claim 13, wherein The electrolyte is a [C3mpyr][FSI]IL having at least about 50 mol % NaFSI salt.

15. A method for forming a battery, comprising the steps of: -Provide an original battery based on sodium ion electrochemistry, the new battery includes: o a counter electrode or positive electrode comprising an electrochemically oxidizable material which releases sodium ions from the material into a superconcentrated electrolyte in the cell during a sodiation step or a charging step, o a hard carbon working electrode or a hard carbon negative electrode, which absorbs sodium ions received at the hard carbon negative electrode from the superconcentrated electrolyte as reduced sodium stored in the hard carbon during the sodiation step or the charging step, and, o an ionic liquid electrolyte containing a super-concentrated sodium salt, comprising at least one ionic liquid and at least one sodium salt, wherein the sodium ion concentration in the superconcentrated ionic liquid electrolyte is 75% or more of its saturation limit in the electrolyte; - producing the formed target battery by polarizing the original battery for up to 5 forming cycles at a high constant current density of 1 / 2C to 5C, preferably 2C, within the full voltage window of the battery, to produce the formed SEI by reducing the electrolyte on the hard carbon electrode, in, (a) The hard carbon negative electrode includes a formed solid electrolyte interface (SEI), wherein the solid electrolyte interface is: - Essentially free of low-order / short-range sulfur (S8 2- To S 2- ) substances, for example, as determined by XPS testing and etching studies; and optionally - substantially free of nitrogen atoms, as determined, for example, by XPS testing and etching studies; and / or (b) After the first formation cycle, the solid electrolyte interface (SEI) / hard carbon electrode has a 200 ohm or less bond with the SEI (R int )-related interfacial resistance, as determined by electrochemical impedance spectroscopy.

16. The method according to claim 15, wherein: Cell polarization occurs by galvanostatically charging and discharging the cell.

17. The method according to claim 15 or claim 16, wherein: The battery is in a half-cell configuration or a full-cell configuration.

18. The method according to any one of claims 15 to 17, wherein: The target battery formed has a nominal C rate of 1 / 2C or 1 / 5C.

19. The method according to any one of claims 15 to 18, wherein: The target battery formed is further cycled at a nominal C-rate constant current of 1 / 2sC or slower for up to 50 cycles, preferably up to 100 cycles, wherein during the nominal C-rate cycling, the target battery formed exhibits a coulombic efficiency (CE) of 99.2% or more, preferably 99.3% or more, preferably 99.4% or more, preferably 99.5% or more, preferably 99.6% or more, preferably 99.7% or more, preferably 99.8% or more, preferably 99.9% or more.

20. The method of any one of claims 15 to 19, further comprising recording charge-discharge cycles during each formation polarization cycle, whereby one or more markers associated with substantially complete and stable SEI formation on the hard carbon electrode are observed in the recorded corresponding charge-discharge cycles, indicating complete formation, wherein the markers include: (a) Discharge-charge curve markers / characteristics - no significant electrolyte reduction slope and / or a substantially static electrolyte reduction slope is observed during the recorded voltage-capacity cycles; Unchanged features / stability of characteristics were observed over the recorded charge-discharge cycles; - No "low voltage" features were present in the recorded charge-discharge cycles (e.g., voltage after initial cycling of an exemplary half-cell was less than about 1.5 V); - the cut-off discharge potential limit of the cell and the resulting discharge capacity are observed to be reached in the absence / presence of curve features associated with sodium ion insertion into the negative active electrode, i.e. in the absence of intercalation features (e.g. sodiation / lithiation); (b) Electrochemical impedance spectroscopy (EIS) markers / characteristics - Evidence of low and / or stable EIS span in electrochemical impedance studies, e.g. involving analysis of Nyquist plots of the recordings; - Evidence of low-resistance SEI formation; - Evidence of a SEI that is more ionically conductive than the formed test cell; and (c) Differential volumetric analysis markers / signatures - The absence of electrolyte reduction / decomposition and / or electrolyte additive reduction / decomposition peaks in the recorded differential capacity curve (dQ / dV); - The absence of metal ion insertion peaks indicates that complete discharge occurs before metal ion insertion; as well as - At higher rates, Na+ ion adsorption / chemisorption peaks appear on the active sites of hard carbon materials, instead of the Na+ insertion peak signal being cut off before the high-rate battery reaches full capacity.

Citation Information

Cited By

  • Hard carbon negative electrode sodium pre-modification compensation control method and system based on first-circle irreversible sodium loss prediction

    CN122474584A